Barrier film and laminate using the same

The barrier film structure, featuring a polypropylene substrate, an underlayer, an aluminum oxide vapor deposition film, and a barrier coating layer, addresses the issues of color unevenness and reduced barrier properties after heat sterilization in conventional films, ensuring effective performance in polyolefin-based packaging materials.

JP2025060413APending Publication Date: 2025-04-10DAI NIPPON PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024126153
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-08-01
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Conventional barrier films with aluminum oxide thin films suffer from color unevenness and reduced barrier properties after heat sterilization, particularly when used in polyolefin-based monomaterial packaging materials.

Method used

A barrier film structure comprising a polypropylene substrate, an underlayer, an aluminum oxide vapor deposition film, and a barrier coating layer, where the aluminum oxide film has a peak top ratio defined by X-ray absorption fine structure analysis within specific limits, and the coating layer has a specific silicon to carbon atom ratio measured by XPS, is developed to address color unevenness and maintain barrier properties after heat sterilization.

Benefits of technology

The proposed barrier film structure effectively reduces color unevenness and maintains the barrier properties of the film even after heat sterilization, making it suitable for use in polyolefin-based monomaterial packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060413000009
    Figure 2025060413000009
  • Figure 2025060413000010
    Figure 2025060413000010
  • Figure 2025060413000011
    Figure 2025060413000011
Patent Text Reader

Abstract

To provide a barrier film which can suppress lowering of barrier property and color unevenness after heating sterilization treatment, and includes a vapor-deposited film and a coating layer formed on an OPP film base material, and a laminate using the same.SOLUTION: There is provided a barrier film in which a biaxially stretched polypropylene base material, a substrate layer, and an aluminum oxide vapor-deposited film are laminated in this order, wherein a peak top ratio P by X-ray absorption fine structure analysis of the aluminum oxide vapor-deposited film is 1.05 or more and less than 1.60. P=(intensity peak top in the vicinity of 1,572 eV) / (intensity peak top in the vicinity of 1,566 eV).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barrier film and a laminate using the same. [Background technology]

[0002] Conventionally, laminated films having a film formed on a substrate such as a long film or sheet of plastic etc. have been used for various purposes. For example, a barrier laminated film has been developed in which a barrier layer made of a thin film of aluminum oxide etc. is provided on a plastic film to provide a barrier function against oxygen and water vapor.

[0003] For example, Patent Document 1 discloses a gas barrier film having excellent transparency and gas barrier properties, which is obtained by using a plasma activated deposition method (a so-called plasma assisted deposition method) that generates high-density plasma in the space between an aluminum evaporation source and a polymer film, as a method for producing a barrier film having an aluminum oxide thin film.

[0004] Furthermore, Patent Document 2 describes that in a method for producing a gas barrier film having a vapor-deposited layer of aluminum oxide, the water vapor partial pressure is desirably 0.001 Pa or less because water vapor reacts with aluminum to increase the degree of hydroxide.

[0005] On the other hand, in recent years, from the viewpoint of environmental consideration, mono-material packaging materials have been considered for the purpose of improving the recyclability of packaging materials. For example, instead of the conventionally widely used polyester film (PET film), a polyolefin film such as a biaxially oriented polypropylene film (OPP film) is applied to the substrate, and a laminate using a polyolefin film such as a non-oriented polypropylene film (CPP film) as a sealant layer to be laminated with this is being considered as a mono-material packaging material.

[0006] For example, Patent Document 3 below discloses a gas barrier laminate comprising a substrate layer containing a polyolefin resin, a barrier layer, and an overcoat layer containing a polyvinyl alcohol resin, the surface hardness of the overcoat layer being 1.5 GPa or less as measured by nanoindentation. A laminate comprising a barrier film in which a biaxially oriented polypropylene substrate, an inorganic oxide vapor deposition film, and a coating layer having barrier properties are laminated in this order, and a sealant layer, is known as a polyolefin-based mono-material packaging material. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-177343 A [Patent Document 2] JP 2022-052319 A [Patent Document 3] WO2022 / 085586 International Publication Summary of the Invention [Problem to be solved by the invention]

[0008] In Patent Document 1, the reactivity between oxygen and aluminum is increased by plasma assist during deposition, and the transparency and barrier properties are improved. However, there is a problem that color unevenness is easily generated in the barrier film and is easily noticeable. Regardless of whether plasma assist is used or not, when performing reactive deposition, the transmittance after deposition is usually measured and feedback is applied to the amount of evaporated aluminum or the amount of introduced oxygen to maintain the transmittance within a certain range, thereby maintaining a uniform appearance. However, in the case of high-speed production at several hundred meters / minute, this feedback may not be able to keep up, and if this causes the transmittance to fluctuate and the film is formed, color unevenness occurs, and when viewed from the end face of the barrier film roll, the appearance becomes like a Baumkuchen. This appearance makes it suspect that the quality is not uniform, which becomes a problem. When a film is formed in a state of high transparency and barrier properties by plasma assist, there is a problem that color unevenness is noticeable and it is difficult to reduce color unevenness after production.

[0009] Furthermore, as described in Patent Document 2, in the aluminum oxide vapor deposition process, it is common practice to reduce the moisture content in the vapor deposition chamber by using, for example, a cold trap or a cryopump.

[0010] On the other hand, when a laminate made of polyolefin-based mono-material packaging materials is applied to heat sterilization treatment such as boiling or retort treatment, OPP film is inferior in heat resistance and strength to PET film, and therefore the barrier property of OPP film after heat sterilization treatment is significantly reduced compared to PET film.

[0011] Regarding this point, in the case of conventional barrier films, the vapor-deposited film suitable for the OPP film used as the vapor deposition substrate and the covering layer that is provided as necessary have not been sufficiently studied. Further study is needed, particularly with regard to the vapor-deposited film and covering layer that can withstand heat sterilization treatment when formed into a laminate.

[0012] In addition, Patent Document 3 specifies the composite elastic modulus and hardness of the coating layer, but focuses on the "processability" of the barrier film. For this reason, Patent Document 3 only specifies the composite elastic modulus and hardness of the coating layer "before heat sterilization treatment," and makes no mention of the heat sterilization treatment or the barrier properties thereafter.

[0013] According to the study by the present inventors, it was found that the composite elastic modulus and hardness of the coating layer vary before and after lamination and depending on the presence or absence of heat sterilization treatment. Therefore, even if the composite elastic modulus and hardness of the coating layer "before heat sterilization treatment" are specified as in Patent Document 3, it is not possible to predict the suppression of the decrease in the barrier property when the laminate is heat sterilized. [Means for solving the problem]

[0014] As a result of intensive research into solving the above problems, the present inventors have found a vapor-deposited film and a coating layer, which are formed on an OPP film substrate and are optionally provided as a barrier film constituting a laminate that is a polyolefin-based mono-material packaging material, that reduce color unevenness in the barrier film and are suitable for use in heat sterilization treatment when formed into a laminate, thereby completing the present invention. Specifically, the present invention provides the following.

[0015] (1) A barrier film comprising a polypropylene substrate, a base layer, and an aluminum oxide vapor-deposited film laminated in this order, The aluminum oxide vapor-deposited film has a peak top ratio P, defined as follows, of 1.05 or more and less than 1.60 when X-ray absorption fine structure analysis is performed on the surface side of the barrier film opposite to the polypropylene substrate side. P = (peak intensity at around 1572 eV) / (peak intensity at around 1566 eV)

[0016] (2) The barrier film according to (1), in which a coating layer having barrier properties is laminated on the aluminum oxide vapor-deposited film.

[0017] (3) The barrier film according to (2), wherein the coating layer has a ratio of silicon atoms to carbon atoms (Si / C) measured by X-ray photoelectron spectroscopy (XPS) of 1.30 or more and 1.65 or less.

[0018] (4) The barrier film according to (1), wherein the underlayer is an anchor coat layer formed on the polypropylene substrate.

[0019] (5) The barrier film according to (1), wherein the underlayer is a surface resin layer containing a polyamide resin formed on the polypropylene substrate.

[0020] (6) The polypropylene base material has at least a first layer and a second layer as two surface layers, and the first layer is formed on the undercoat layer side, the first layer comprises a copolymer of propylene and another monomer; The undercoat layer is the anchor coat layer, The barrier film according to (4), wherein the first layer of the polypropylene base material, the anchor coat layer, the aluminum oxide vapor deposition film, and the coating layer having barrier properties are laminated in this order.

[0021] (7) The polypropylene base material has at least a first layer and a second layer as two surface layers, and the first layer is formed on the undercoat layer side, the first layer comprises modified polypropylene; the undercoat layer is the surface resin layer containing the polyamide resin, The barrier film according to (5), wherein the first layer of the polypropylene base material, the surface resin layer containing the polyamide resin, the aluminum oxide vapor deposition film, and the coating layer having barrier properties are laminated in this order.

[0022] (8) The polypropylene base material has at least a first layer and a second layer as two surface layers, and the second layer is formed on the surface opposite to the undercoat layer side, the second layer comprises a copolymer of propylene and another monomer; The barrier film according to (1), wherein the first layer of the polypropylene base material, the undercoat layer, the aluminum oxide vapor deposition film, and the coating layer having barrier properties are laminated in this order.

[0023] (9) A heat-sterilized laminate comprising the barrier film according to any one of (1) to (8) and a sealant layer, the laminate being used for a packaging bag for containing retort food or boiled food, A laminate, wherein the coating layer of the laminate has a composite elastic modulus and an indentation hardness, as measured by a nanoindentation method from a cross-section of the coating layer, such that the composite elastic modulus is 5.0 GPa or more and 8.5 GPa or less, and the indentation hardness is 0.9 GPa or more and 1.7 GPa or less.

[0024] (10) A packaging product comprising the laminate described in (9). Effect of the Invention

[0025] The barrier film of the present invention comprises a vapor-deposited film formed on an OPP film substrate and a coating layer that is provided as needed, while reducing color unevenness and, in the case of a laminate, suppressing a decrease in barrier properties after heat sterilization treatment. [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a barrier film according to an embodiment of the present invention. [Diagram 2] 1 is a diagram showing an example of a film forming apparatus according to an embodiment of the present invention; [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a plasma pretreatment mechanism of a film forming apparatus. [Figure 4] 2 is a plan view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Diagram 5] 2 is a cross-sectional view showing an example of an electrode unit and a magnetic field generating unit of a plasma pretreatment mechanism of a film forming apparatus. FIG. [Figure 6] FIG. 2 is a cross-sectional view showing an example of a film formation mechanism of a film formation apparatus. [Figure 7] FIG. 1 is a cross-sectional view showing an example of a laminate using the barrier film of the present invention. [Figure 8] FIG. 2 is a cross-sectional view showing another example of a laminate using the barrier film of the present invention. [Figure 9] FIG. 1 shows an XAFS spectrum of the barrier film of Example 2. [Figure 10] FIG. 1 shows the results of XAFS spectrum analysis of the barrier film of Example 2. [Figure 11] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Example 3. [Figure 12] FIG. 2 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Comparative Example 1. [Figure 13] FIG. 13 is a diagram showing the results of XAFS spectrum analysis of the barrier film of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as appropriate within the scope of the object of the present invention. In addition, in this specification, the expression "X to Y" (X and Y are arbitrary numbers) means "X or more and Y or less."

[0028] FIG. 1 is a cross-sectional view showing an example of a barrier film according to the present embodiment. A barrier film manufactured using the film forming apparatus according to the present embodiment includes, for example, a substrate 100 corresponding to the biaxial polypropylene substrate of the present invention, an underlayer 115, a vapor deposition film 120, and, if necessary, a coating layer 130, as in the barrier film 100A shown in FIG. 1. In the example shown in FIG. 1, the underlayer 115 is located on one surface of the substrate 100. In the example shown in FIG. 1, the barrier film 100A is formed by laminating the substrate 100, the underlayer 115, the vapor deposition film 120, and the coating layer 130 in this order, and the coating layer 130 is located on the surface of the barrier film. The vapor deposition film 120 and the coating layer 130 constitute a barrier layer.

[0029] In this specification, "laminated in this order" means that the polypropylene base material, the undercoat layer, the aluminum oxide vapor deposition film, and the coating layer having barrier properties are laminated in this order, and further layers such as an anchor coat layer described below may be laminated between these layers.

[0030] Each layer constituting the barrier film 100A will be described below.

[0031] [Polypropylene base material] The polypropylene base material 100 is a polypropylene base material that has been subjected to a biaxial stretching treatment. Hereinafter, except when the stretching treatment is mentioned, when the term "polypropylene base material" is simply used, it means a polypropylene base material that has been subjected to a biaxial stretching treatment.

[0032] The polypropylene base material is composed of at least polypropylene. The polypropylene may be any one of a propylene homopolymer, a propylene random copolymer, and a propylene block copolymer, and may be a mixture of two or more selected from these.

[0033] A propylene homopolymer is a polymer of propylene alone. A propylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene. A propylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of at least an α-olefin other than propylene. The latter polymer block may be a polymer block of propylene and an α-olefin other than propylene.

[0034] Examples of the α-olefins include α-olefins having 2 to 20 carbon atoms, specifically, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene.

[0035] Among polypropylenes, it is preferable to use a random copolymer from the viewpoint of transparency. When the rigidity and heat resistance of the laminate are important, it is preferable to use a homopolymer. When the impact resistance of the laminate is important, it is preferable to use a block copolymer.

[0036] In one embodiment, the melt flow rate (MFR) of polypropylene may be 0.1 g / 10 min or more and 50 g / 10 min or less, or 0.3 g / 10 min or more and 30 g / 10 min or less, from the viewpoint of film-forming property and processability. The MFR of polypropylene is measured in accordance with ASTM D1238 under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0037] As the polypropylene, biomass-derived polypropylene or mechanically recycled or chemically recycled polypropylene may be used.

[0038] The polypropylene content in the polypropylene base material is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and still more preferably 95% by mass or more.

[0039] The polypropylene base material may contain a resin material other than polypropylene, such as polyolefins such as polyethylene, (meth)acrylic resins, vinyl resins, cellulose resins, polyamides, polyesters, and ionomer resins.

[0040] The polypropylene base material may contain additives, such as crosslinkers, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, lubricants, antistatic agents, pigments, and modifying resins.

[0041] The polypropylene substrate is a substrate that has been subjected to a biaxial stretching treatment. This can improve, for example, the heat resistance, impact resistance, water resistance, and dimensional stability of the barrier substrate. A laminate including such a barrier substrate is suitable, for example, as a packaging material that is subjected to a boiling treatment or a retort treatment.

[0042] The stretching ratio in the longitudinal direction (flow direction of the substrate, MD direction) is preferably 2 to 15 times, more preferably 5 to 13 times. The stretching ratio in the transverse direction (direction perpendicular to the MD direction, TD direction) is preferably 2 to 15 times, more preferably 5 to 13 times. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the polypropylene substrate can be further improved, and when the polypropylene substrate is used as the outermost layer, the printability of the polypropylene substrate can be improved. From the viewpoint of the breaking limit of the polypropylene substrate, the stretching ratio is preferably 15 times or less.

[0043] The thickness of the polypropylene substrate is preferably 10 μm or more and 100 μm or less, more preferably 10 μm or more and 50 μm or less, and even more preferably 15 μm or more and 25 μm or less. When the thickness is equal to or more than the lower limit, for example, the strength and heat resistance of the barrier substrate can be improved. When the thickness is equal to or less than the upper limit, for example, the processability of the barrier substrate can be improved.

[0044] The polypropylene substrate may be a coextrusion stretched film. It can be produced by forming a laminated film using a conventionally known T-die method or inflation method, and then stretching the laminated film. When forming the film by the inflation method, the laminated film may be stretched at the same time.

[0045] The polypropylene substrate may be surface-treated. This can improve the adhesion between the polypropylene substrate and other layers, for example. Examples of surface treatment methods include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using one or more gases selected from oxygen gas, argon gas, nitrogen gas, and the like, and glow discharge treatment; and chemical treatments such as oxidation treatment using chemicals. In addition, an easy-adhesion layer may be provided on the surface of the polypropylene substrate.

[0046] When the polypropylene base material is used as the outermost layer of the laminate, a printed layer may be provided on the second layer. The image formed on the printed layer is not particularly limited, and may be a character, a pattern, a symbol, or a combination thereof. The printed layer may be formed using an ink derived from biomass. This can further reduce the environmental load.

[0047] Examples of methods for forming the printed layer include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of reducing the environmental load.

[0048] The polypropylene substrate is preferably transparent. Specifically, it is preferable that the total light transmittance measured based on JIS K 7361-1:1997 is high. Specifically, the total light transmittance is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more.

[0049] The substrate 100 of the roll is preferably moisture-conditioned in a process for forming an undercoat layer or a moisture-conditioning process after the formation of the undercoat layer. This can improve the barrier properties. Also, it can prevent the substrate from breaking due to sticking during unwinding in the deposition process described below. One example of moisture-conditioning conditions is storage at a temperature of 22 to 30°C and a relative humidity of 40 to 65% RH for 1 to 7 days. Note that rewinding the roll before storage is also effective for moisture conditioning. In this case, the rewinding process is also preferably performed under the above moisture-conditioning conditions.

[0050] The polypropylene substrate may be a multilayer film having at least a first layer and a second layer. The first layer is a layer on one side of the polypropylene substrate (the side on which a barrier layer such as a vapor deposition film is formed), and the second layer is a layer on the other side of the polypropylene substrate.

[0051] The first layer and the second layer may each be a propylene random copolymer, which is a random copolymer of propylene and an α-olefin other than propylene. When the first layer and the second layer are random copolymers, the adhesion between the layer and other layers in contact therewith can be improved. Examples of α-olefins include ethylene, 1-butene, and 1-hexene.

[0052] The first layer may be a modified polypropylene, which improves adhesion to the polyamide resin when the undercoat layer described below is made of a polyamide resin.

[0053] The polypropylene substrate may include a third layer as an intermediate layer between the first layer and the second layer. The intermediate layer preferably includes a homopolymer of polypropylene. The intermediate layer may have a single layer structure or a multilayer structure.

[0054] A specific example of a three-layer structure is a propylene random copolymer / propylene homopolymer / propylene random copolymer in the order of the first layer / third layer / second layer from the surface on which the vapor deposition film is formed. In this case, when the first layer is a propylene random copolymer and the undercoat layer described below is an anchor coat layer, the adhesion to the anchor coat layer is improved. In addition, when the second layer is a propylene random copolymer, the adhesion to the first adhesive layer 161 for laminating the sealant layer 150 is improved, for example, when forming the laminate shown in FIG. 7 described below.

[0055] Another example of a specific three-layer structure is modified polypropylene / propylene homopolymer / propylene random copolymer, in the order of first layer / third layer / second layer from the side on which the vapor-deposited film is formed. In this case, when the first layer is modified polypropylene and the underlayer is made of polyamide resin, the adhesion to the polyamide resin is improved. In addition, when the third layer is made of propylene random copolymer, the adhesion to the first adhesive layer 161 for laminating the sealant layer 150 is improved, for example, when forming the laminate shown in FIG. 7, which will be described later.

[0056] [Base layer] The base layer 150 is formed on the surface of the substrate 100 on which the deposition film 120 is formed. When the base layer is a surface resin layer made of a high melting point resin material described later, the deposition resistance is improved, which promotes migration of the deposition material, and a deposition film consisting of a continuous layer that is dense, has few gaps, and is highly flexible is obtained. In addition, since the base layer is a high melting point resin material, the resistance to heat sterilization treatment is also improved. When the base layer is an anchor coat layer by coating described later, the surface of the substrate can be made smoother, which promotes migration of the deposition material, and the adhesive strength between the polypropylene substrate and the deposition film is increased, and a deposition film consisting of a continuous layer that is dense, has few gaps, and is highly flexible is obtained. As a result, high gas barrier properties are obtained, and breakage of the deposition film and coating layer due to deformation or bending of the film, and the resulting decrease in gas barrier properties can be suppressed. In addition, a barrier film with excellent heat resistance that can withstand heat sterilization treatment can be obtained.

[0057] (Surface resin layer) The underlayer is preferably a surface resin layer. By providing a surface resin layer on a polypropylene base material, which preferably contains a resin material having a melting point of 180° C. or higher (hereinafter also referred to as a high melting point resin material), a dense vapor deposition film with few gaps can be formed on the surface resin layer, thereby improving the gas barrier property.

[0058] The melting point of the high melting point resin material is more preferably 100°C or higher, even more preferably 180°C or higher, and particularly preferably 200°C or higher. By setting the melting point of the high melting point material to 100°C or higher, when the second layer has a copolymer of propylene and other monomers or modified polypropylene, the second layer can be protected from the deposition material. By setting the melting point of the high melting point resin material to 180°C or higher, the density of the deposition film can be improved, and the gas barrier property can be further improved. In addition, the resistance of the laminate to heat sterilization treatment can be further improved. From the viewpoint of film formability, the melting point of the high melting point resin material is preferably 265°C or lower, more preferably 260°C or lower, and even more preferably 250°C or lower. In this specification, the melting point can be measured in accordance with JIS K7121:2012 (Method of measuring transition temperature of plastics). Specifically, the melting point can be obtained by measuring a DSC curve at a heating rate of 10°C / min using a differential scanning calorimetry (DSC) device.

[0059] The difference between the melting point of the high melting point resin material contained in the surface resin layer and the melting point of the polypropylene contained in the biaxially oriented polypropylene base material is preferably 20 to 100°C, more preferably 20 to 70°C. When the melting point difference is 20°C or more, the denseness of the vapor-deposited film can be further improved, and the gas barrier property can be further improved. In addition, the resistance of the laminate to heat sterilization treatment can be further improved. When the melting point difference is 100°C or less, the film formability can be further improved.

[0060] The high melting point resin material preferably has a polar group. In the present invention, the polar group refers to a group containing one or more heteroatoms, and examples thereof include ester groups, epoxy groups, hydroxyl groups, amino groups, amide groups, carboxyl groups, carbonyl groups, carboxylic anhydride groups, sulfone groups, thiol groups, and halogen groups. Among these, from the viewpoint of the laminate strength of the packaging container, hydroxyl groups, ester groups, amino groups, amide groups, carboxyl groups, and carbonyl groups are preferred, and hydroxyl groups are more preferred.

[0061] The high melting point resin material can be used without any particular limitation as long as it has a melting point of 180° C. or higher. Examples of the high melting point resin material include vinyl resin, polyamide, polyimide, polyester, (meth)acrylic resin, cellulose resin, polyolefin resin, and ionomer resin.

[0062] In the present invention, the high melting point resin material is particularly preferably a resin material having a melting point of 180° C. or higher and having a polar group, and is preferably an ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyester, or polyamide, and more preferably a polyamide such as nylon 6 (hereinafter, "nylon" is a registered trademark), nylon 6,6, aromatic-containing nylon, or amorphous nylon. By using such a resin material, the gas barrier property of the vapor-deposited film formed on the surface resin layer can be effectively improved.

[0063] In addition, by using polyamide as the high melting point resin material, the deterioration of the gas barrier property can be suppressed even when the barrier laminate is heated. As the high melting point resin material, polyamide containing a benzene ring (aromatic) is preferable from the viewpoint of mechanical strength and gas barrier property. Polyamide containing a benzene ring can be combined with other materials and co-extrusion molded. An example of polyamide containing a benzene ring is Nylon MXD6 manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0064] The polyamide containing a benzene ring is a polyamide containing a benzene ring in either or both of the constituent units derived from a diamine or the constituent units derived from a dicarboxylic acid. It may be a copolymer of one or more diamines and one or more dicarboxylic acids. It may also be a mixture of two or more copolymers. Examples of the copolymer include a copolymer of a diamine containing a benzene ring and an aliphatic dicarboxylic acid, a copolymer of an aliphatic diamine and a dicarboxylic acid containing a benzene ring, a copolymer of a diamine containing a benzene ring, a dicarboxylic acid containing a benzene ring and an aliphatic dicarboxylic acid, and a copolymer of an aliphatic diamine, a diamine containing a benzene ring and a dicarboxylic acid containing a benzene ring.

[0065] The surface resin layer may contain a polyamide that does not contain a benzene ring, and may also contain polyester, acrylic resin, ionomer resin, etc., to the extent that it does not affect processability and physical properties.

[0066] The diamine containing a benzene ring is metaxylenediamine, paraxylenediamine, metaphenylenediamine, paraphenylenediamine, etc. One or more of these are used.

[0067] The dicarboxylic acid containing a benzene ring refers to aromatic dicarboxylic acids such as terephthalic acid (TPA) and isophthalic acid (IPA), and naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. At least one of these is used.

[0068] Aliphatic diamines include linear aliphatic diamines such as 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine (hexamethylenediamine), 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine (NDA), 1,10-decanediamine (DDA), 1,11-undecanediamine, and 1,12-dodecanediamine, 2-methyl-1,8-octanediamine (MODA), 4- These include branched aliphatic diamines such as methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, 2,2,4- / 2,4,4-trimethyl-1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 2-methyl-1,6-hexanediamine, and 2-methyl-1,7-heptanediamine, and alicyclic diamines such as isophoronediamine, norbornanedimethylamine, and tricyclodecanedimethylamine. At least one of these can be used.

[0069] The aliphatic dicarboxylic acid is an aliphatic dicarboxylic acid having 2 to 20 carbon atoms. In consideration of polymerization suitability and processability, adipic acid is most preferable, but other dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecadioic acid, hexadecadioic acid, eicosanedioic acid, eicosadienedioic acid, 2,2,4-trimethyladipic acid, etc. One or more of these are used.

[0070] Polyamides not containing a benzene ring include polyamides 6, 7, 10, 11, 12, 410, 56, 66, 69, 610, 611, 612, 1010, etc. The surface resin layer may contain one or more of these.

[0071] The surface resin layer preferably contains 20% by mass or more of polyamide containing a benzene ring, more preferably 30% by mass or more, and even more preferably 40% by mass or more, based on the entire surface resin layer. By containing 20% ​​by mass or more of polyamide containing a benzene ring, moist heat swelling can be suppressed, so that adhesion to the vapor deposition film can be improved and the deterioration of the barrier performance of the vapor deposition film during heat sterilization by boiling or retort can be reduced. If it is less than 20% by mass, adhesion to the vapor deposition film may be poor and the barrier performance may be deteriorated during heat sterilization.

[0072] The surface resin layer preferably contains 20% by mass or more of crystalline polyamide, more preferably 30% by mass or more, and even more preferably 40% by mass or more. By containing 20% ​​by mass or more of crystalline polyamide, gas barrier properties can be improved and wet heat swelling can be suppressed. Examples of crystalline polyamide include copolymers of metaxylenediamine and adipic acid, copolymers of hexamethylenediamine and terephthalic acid, polyamide 6, etc.

[0073] The surface resin layer preferably contains 90% by mass or less of crystalline polyamide, more preferably 80% by mass or less, and even more preferably 70% by mass or less, whereby an amorphous polyamide, which will be described later, can be mixed.

[0074] The surface resin layer preferably contains 10% by mass or more of amorphous polyamide, more preferably 20% by mass or more, and even more preferably 30% by mass or more. By containing 10% by mass or more of amorphous polyamide, the extrusion suitability and stretchability are improved, and the production of the base film 10 is facilitated. Examples of amorphous polyamide include a copolymer of hexamethylenediamine and isophthalic acid, a copolymer of metaxylenediamine and isophthalic acid, a copolymer of hexamethylenediamine and a dicarboxylic acid having a molar ratio of isophthalic acid / terephthalic acid of 2 / 1, and a copolymer of metaxylenediamine and a dicarboxylic acid having a molar ratio of adipic acid / isophthalic acid of 1 / 1.

[0075] The surface resin layer preferably contains 80% by mass or less of amorphous polyamide, more preferably 70% by mass or less, and even more preferably 60% by mass or less, whereby crystalline polyamide can be mixed.

[0076] The thickness of the surface resin layer is preferably 0.1 μm to 5 μm, more preferably 0.2 μm to 4 μm. By making the thickness of the surface resin layer 0.1 μm or more, the density of the vapor-deposited film can be further improved, and the gas barrier property can be further improved. By making the thickness 5 μm or less, the film-forming property and the processability can be further improved.

[0077] The surface resin layer can be formed by melt extrusion. It may be extruded onto a biaxially oriented polypropylene film to form the polypropylene substrate of the present invention, or it may be coextruded together with polypropylene in a multilayer structure and then stretched to form the polypropylene substrate of the present invention.

[0078] The undercoat layer may be an anchor coat layer. The anchor coat layer can be formed by coating using a resin material having a polar group. As the resin material having a polar group, ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVA), polyester, polyethyleneimine, hydroxyl group-containing (meth)acrylic resin, nylon 6, nylon 6,6, aromatic-containing nylon, amorphous nylon, polyurethane, etc. are preferable, and hydroxyl group-containing (meth)acrylic resin, ethylene-vinyl alcohol copolymer, polyvinyl alcohol are more preferable. As the resin material having a polar group, from the viewpoint of gas barrier property after heat sterilization treatment due to smoothness and high cohesive energy, (meth)acrylic resin containing urethane group and hydroxyl group is particularly preferable.

[0079] From the viewpoint of adhesion to the vapor-deposited film, it is preferable to add a silane coupling agent to the anchor coat layer. As the silane coupling agent, the silane coupling agents described below can be used.

[0080] In the present invention, the anchor coat layer can be formed using a water-based emulsion or a solvent-based emulsion. Specific examples of the water-based emulsion include a polyamide-based emulsion, a polyethylene-based emulsion, and a polyurethane-based emulsion, and specific examples of the solvent-based emulsion include a polyester-based emulsion.

[0081] As the polyurethane emulsion, for example, a mixture of a polyurethane emulsion and an emulsion of an oxazoline group-containing polymer is preferably used. The polyurethane emulsion may further contain a silane coupling agent.

[0082] The thickness of the anchor coat layer is preferably 0.02 μm or more and 10 μm or less, more preferably 0.05 μm or more and 8 μm or less, even more preferably 0.1 μm or more and 5 μm or less, and even more preferably 0.2 μm or more and 3 μm or less. By making the thickness of the anchor coat layer 0.02 μm or more, the smoothness can be further improved, and the gas barrier property after deposition can be further improved. By making the thickness of the anchor coat layer 10 μm or less, the processability and productivity can be further improved.

[0083] The anchor coat layer may be formed by coating (applying, coating) on ​​a biaxially oriented polypropylene substrate, or may be formed by coating on a polypropylene film and then biaxially oriented.

[0084] [Vapor deposition film] Next, the deposited film 120 will be described. The deposited film contains aluminum oxide, which is an inorganic oxide. In the deposited film, aluminum is present in a state in which at least a part of it forms Al2O3. The deposited film may further contain metal oxides such as silicon oxide, silicon nitride, silicon oxynitride, silicon carbide, magnesium oxide, titanium oxide, tin oxide, indium oxide, zinc oxide, and zirconium oxide, or nitrides and carbides of these metals.

[0085] The lower limit of the thickness of the evaporated film is preferably 3 nm or more, more preferably 5 nm or more, and the upper limit is preferably 100 nm or less, more preferably 50 nm or less, particularly preferably 15 nm or less.

[0086] In the present invention, the term "aluminum oxide vapor deposition film" means, as described above, "a vapor deposition film containing aluminum oxide", and may contain aluminum oxide hydroxide AlO(OH) and aluminum hydroxide Al(OH)3 in addition to aluminum oxide Al2O3. This will be explained in detail below.

[0087] (XAFS Spectral Analysis) XAFS analysis is an X-ray absorption fine structure (XAFS) spectrum, in which X-rays are irradiated from the surface side of the deposition surface of the barrier film (the coating layer side if there is a coating layer) and the amount of absorption is measured. Detailed measurement and analysis conditions are described in the examples.

[0088] In particular, XAFS spectrum analysis of soft X-rays using synchrotron radiation can provide bulk information on the entire deposited film, not just a portion of the surface side of the deposited film, and can provide information on the size of hydroxyl groups in the aluminum oxide deposited film. Even if a coating layer or the like is present on the surface of the deposited film, information on the deposited film can be obtained even with the coating layer present by irradiating the deposited film from the surface side of the coating layer through the coating layer.

[0089] Fig. 9 is an example of the results of XAFS measurement of the barrier film of Example 2 described below. Fig. 10 shows each peak obtained by peak separation of the XAFS spectrum in Example 2. In Figs. 9 and 10, the vertical axis is absorption intensity (au) and the horizontal axis is energy (eV). The peak top ratio P in the present invention is the ratio obtained from each peak top after peak separation of the XAFS spectrum, for example, as shown in Fig. 10.

[0090] In the peak separation analysis in Figure 10, Experiment is the measured XAFS spectrum, Fit.Peak1 is the separated peak with an intensity of 1566 eV, Fit.Peak2 is the separated peak with an intensity of 1568 eV, and Fit.Peak3 is the separated peak with an intensity of 1572 eV. Fit.Base1 is the baseline at 1566 eV, and Fit.Base2 is the baseline at 1568 eV.

[0091] 9 and 10, the XAFS spectrum has multiple peaks, specifically, peak P1 with a top near 1566 eV, peak P2 with a top near 1568 eV, and peak P3 with a top near 1572 eV. Note that "near 1566 eV" refers to 1565 eV or more and 1567 eV or less, "near 1568 eV" refers to more than 1567 eV and 1569 eV or less, and "near 1572 eV" refers to 1571 eV or more and 1573 eV or less.

[0092] Here, P1 is considered to be a peak derived from 4-coordinate aluminum oxide, P2 from 6-coordinate aluminum oxide, and P3 from 6-coordinate aluminum hydroxide and aluminum oxide hydroxide.

[0093] It is believed that an amorphous aluminum oxide film has better flexibility than a crystalline film, so it is preferable for it to be amorphous when used as a barrier film. However, it has been difficult to confirm whether a film is crystalline or amorphous using XRD, a conventional X-ray analysis, except when a clear crystalline peak can be confirmed.

[0094] When checking the XAFS spectrum, γ-Al2O3 and θ-Al2O3 are examples of crystalline aluminum oxide films in which P1 is detected, but the P1 peak is never relatively higher than the P2 peak. According to the examples of the present application described later, for example, in Example 2 (see FIG. 10), it is clear that P1>P2, and it can be confirmed that an amorphous film has been formed.

[0095] Furthermore, being amorphous is not enough to create a flexible aluminum oxide film, and the introduction of hydroxyl groups is considered necessary.However, for example, in depth analysis using conventional TOF-SIMS, it is unclear whether the aluminum oxide film is being evaluated or the moisture remaining at the interface between the aluminum oxide film and the substrate is being detected, and sufficient depth resolution cannot be obtained in the aluminum oxide film when a coating layer is present, making it impossible to fully investigate the correlation between film formation conditions and film quality.

[0096] According to the present invention, by checking the XAFS spectrum and defining the peak top ratio P as P3 peak top / P1 peak top=(intensity peak top at about 1572 eV) / (intensity peak top at about 1566 eV), information regarding the amount of hydroxyl groups in the aluminum oxide vapor-deposited film can be obtained.

[0097] The inventors have found that, in order to reduce color unevenness, it is more effective to form the film in a state where there are many dangling bonds in the aluminum oxide film and the water vapor barrier property is low, and then promote oxidation and hydroxylation (mainly hydroxylation) by aging to reduce the dangling bonds and develop water vapor barrier property, rather than forming the film in a state where the water vapor barrier property is high immediately after deposition. For this reason, the inventors have investigated the correlation between the film formation conditions, including moisture during deposition and aging, and the film quality by checking the XAFS spectrum, and have completed the present invention.

[0098] The present invention has found that the color loss of the barrier film changes depending on the value of the peak top ratio P. Specifically, by setting the peak top ratio P to 1.05 or more and 1.60 or less, it is possible to improve the barrier properties after heat sterilization treatment and improve the color unevenness of the barrier film at the same time. The lower limit of the peak top ratio P is preferably 1.10 or more, more preferably 1.20 or more. The upper limit of the peak top ratio P is preferably 1.50 or less.

[0099] If the peak top ratio P is less than 1.05, color unevenness is noticeable immediately after deposition due to the high oxidation film, and color fading is difficult to occur due to the high barrier properties. Note that "color fading" refers to an improvement in transparency (transmittance) or a fading in color due to changes over time after deposition. This transparency or color affects the appearance of the end face (side face) in the wound state. Details will be explained in the evaluation of "color unevenness" in the examples. If the peak top ratio P exceeds 1.60 after high temperature and high humidity moist heat treatment, too many hydroxyl groups are introduced, reducing the initial barrier properties, especially the water vapor barrier properties.

[0100] The peak top ratio P of the barrier film can be adjusted by controlling the combination of moisture conditioning of the polypropylene substrate including the underlayer, plasma pretreatment, plasma assisted treatment during deposition, aging treatment after the film formation process, and aging treatment after the coating layer formation process. In particular, not using a cold trap in the film formation process can improve the barrier properties and reduce color unevenness of the barrier film. These results will be described in detail in the manufacturing method and examples below.

[0101] [Coating layer] The covering layer 130 formed on the deposited film 120 is a covering layer (barrier coat layer) that protects the deposited film mechanically and chemically and also improves the barrier performance.

[0102] The coating layer is formed by applying a barrier coating agent onto the vapor deposition film and solidifying it. For example, it may be a cured product of a resin composition containing an alkoxysilane and a hydroxyl group-containing water-soluble resin (water-soluble polymer), and further containing a silane coupling agent, a sol-gel catalyst, an acid, etc., as necessary. Other barrier coating agents may be formed using a water-based emulsion or a solvent-based emulsion.

[0103] Specific examples of the water-based emulsion include polyamide-based emulsion, polyethylene-based emulsion, and polyurethane-based emulsion, and specific examples of the solvent-based emulsion include polyester-based emulsion.

[0104] As the polyurethane emulsion, for example, a mixture of a polyurethane emulsion and an emulsion of an oxazoline group-containing polymer is preferably used. The polyurethane emulsion may further contain a silane coupling agent.

[0105] As the metal alkoxide, the general formula R1 n M(OR 2 ) m(wherein, in the formula, R1 and R2 represent an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M), and examples of the metal atom represented by M of the metal alkoxide include silicon, zirconium, titanium, aluminum, and the like. For example, it is preferable to use an alkoxysilane in which M is Si.

[0106] The above alkoxysilane is, for example, one represented by the general formula Si(ORa)4 (wherein Ra represents a lower alkyl group). In the above, Ra may be a methyl group, an ethyl group, an n-propyl group, an n-butyl group, or the like. Specific examples of the above alkoxysilane include tetramethoxysilane Si(OCH3)4, tetraethoxysilane Si(OC2H5)4, tetrapropoxysilane Si(OC3H7)4, tetrabutoxysilane Si(OC4H9)4, and the like. The above alkoxides may be used in combination of two or more kinds.

[0107] Silane coupling agents having reactive groups such as vinyl, epoxy, methacryl, and amino groups can be used. In particular, organoalkoxysilanes having epoxy groups are suitable, and for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropyldimethylmethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyldimethylethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be used. The above-mentioned silane coupling agents may be used alone or in combination of two or more.

[0108] In particular, the crosslink density of the cured film of the coating layer using bifunctional compounds such as γ-glycidoxypropylmethyldimethoxysilane and γ-glycidoxypropylmethyldiethoxysilane is lower than that of the system using trialkoxysilane. Therefore, the cured film has excellent gas barrier properties and hot water treatment resistance, and is flexible and has excellent bending resistance, so that the gas barrier properties are not easily deteriorated.

[0109] The water-soluble polymer may be a polyvinyl alcohol resin or an ethylene-vinyl alcohol copolymer, or may be a combination of a polyvinyl alcohol resin and an ethylene-vinyl alcohol copolymer. In the coating layer according to the present embodiment, a polyvinyl alcohol resin is preferred.

[0110] Generally, the polyvinyl alcohol resin can be one obtained by saponifying polyvinyl acetate. The polyvinyl alcohol resin can be a partially saponified polyvinyl alcohol resin in which several tens of percent of acetate groups remain, a completely saponified polyvinyl alcohol in which no acetate groups remain, or a modified polyvinyl alcohol resin in which OH groups have been modified. As the polyvinyl alcohol resin, it is necessary to use at least one that undergoes crystallization to improve the film hardness of the gas barrier coating film, and preferably has a saponification degree of 70% or more. In addition, any polyvinyl alcohol resin can be used as long as it has a polymerization degree within the range used in the conventional sol-gel method (about 100 to 5000). Examples of such polyvinyl alcohol resins include RS resin "RS-110 (saponification degree = 99%, polymerization degree = 1,000)" manufactured by Kuraray Co., Ltd. and "GOHSENOL NM-14 (saponification degree = 99%, polymerization degree = 1,400)" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0111] The ethylene-vinyl alcohol copolymer may be a saponified copolymer of ethylene and vinyl acetate, i.e., a product obtained by saponifying an ethylene-vinyl acetate random copolymer. For example, it may be a partially saponified product in which several tens of mol% of acetate groups remain, or a completely saponified product in which only a few mol% of acetate groups remain or no acetate groups remain, and is not particularly limited. However, from the viewpoint of barrier properties, the lower limit of the saponification degree is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. The upper limit is 100% or less.

[0112] As the sol-gel catalyst, an acid or amine compound is preferable.

[0113] As the acid, for example, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used.

[0114] The content of the acid is preferably 0.001 to 0.05 mol%, more preferably 0.01 to 0.03 mol%, based on the total molar amount of alkoxy groups in the metal alkoxide. If the content is less than 0.001%, the catalytic effect is too small, whereas if the content is more than 0.05 mol%, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0115] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable. Specifically, for example, N,N-dimethylbenzylamine, tripropylamine, tributylamine, tripentylamine, etc. can be used. In particular, N,N-dimethylbenzylamine is preferable.

[0116] The content of the amine compound is preferably, for example, 0.01 to 1.0 part by mass, particularly 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. If the content is less than 0.01 part by mass, the catalytic effect is too small, whereas if the content is more than 1.0 part by mass, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0117] As the solvent, it is preferable to use water or alcohol such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropanol, or n-butanol.

[0118] The barrier coating layer formed as described above has a layer thickness of 100 to 500 nm, preferably 200 to 400 nm. This range is preferable because the coating film does not crack and sufficiently covers the surface of the deposited film.

[0119] When the barrier coating agent contains a silane coupling agent, 5 to 10 parts by mass of a water-soluble polymer such as a polyvinyl alcohol resin and 1 to 10 parts by mass of the silane coupling agent can be used per 100 parts by mass of alkoxysilane. This allows the flexibility of the film to be maintained. In the above, if the silane coupling agent is used in an amount exceeding 20 parts by mass, the rigidity and brittleness of the barrier coating film formed increases, which is not preferable.

[0120] Furthermore, when a silane coupling agent is not contained, the ratio of metal alkoxide can be reduced and the barrier properties can be improved by using 10 to 20 parts by mass of a water-soluble polymer such as a polyvinyl alcohol resin per 100 parts by mass of alkoxysilane.

[0121] The lower limit of the ratio of the mass of the metal alkoxide such as tetraethoxysilane in terms of SiO2 to the mass of the water-soluble resin such as polyvinyl alcohol in the coating layer is preferably 1.6 or more, more preferably 1.9 or more. The upper limit is preferably 3.9 or less, more preferably 3.5 or less. If the ratio exceeds 3.9, the barrier property may decrease in the post-processing, and if the ratio is less than 1.6, the barrier property after the retort treatment may decrease, which is undesirable.

[0122] The silicon atom to carbon atom ratio (Si / C) of the coating layer is preferably 1.30 or more and 1.65 or less. If it exceeds 1.65, the barrier properties may decrease in the post-processing, etc., which is not preferable, and if it is less than 1.30, the barrier properties after the heat sterilization treatment decrease, which is not preferable. The silicon atom / carbon atom ratio of the coating layer can be measured by X-ray photoelectron spectroscopy (XPS), specifically, under the conditions described in the examples.

[0123] (Film forming equipment) Next, an example of a film forming apparatus 10 used in the manufacturing method of a barrier film will be described. As shown in Fig. 2, the film forming apparatus 10 includes a substrate transport mechanism 11A for transporting the substrate 1, a plasma pretreatment mechanism 11B for performing plasma pretreatment on the surface of the substrate 1, and a film forming mechanism 11C for forming a vapor deposition film 2. In the example shown in Fig. 5, the film forming apparatus 10 further includes a decompression chamber 12. The decompression chamber 12 has a decompression mechanism, such as a vacuum pump described later, for adjusting the atmosphere in at least a part of the space inside the decompression chamber 12 to atmospheric pressure or lower.

[0124] In the example shown in Fig. 2, the decompression chamber 12 includes a substrate transport chamber 12A in which the substrate transport mechanism 11A is located, a plasma pretreatment chamber 12B in which the plasma pretreatment mechanism 11B is located, and a film formation chamber 12C in which the film formation mechanism 11C is located. The decompression chamber 12 is preferably configured to suppress the atmospheres inside the respective chambers from mixing with each other. For example, as shown in Fig. 2, the decompression chamber 12 may be located between the substrate transport chamber 12A and the plasma pretreatment chamber 12B, between the plasma pretreatment chamber 12B and the film formation chamber 12C, and between the substrate transport chamber 12A and the film formation chamber 12C, and may have partition walls 35a to 35c that separate the respective chambers.

[0125] The substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C will be described. The plasma pretreatment chamber 12B and the film formation chamber 12C are each provided in contact with the substrate transfer chamber 12A, and each has a portion connected to the substrate transfer chamber 12A. This allows the substrate 1 to be transferred between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, and between the substrate transfer chamber 12A and the film formation chamber 12C without being exposed to the atmosphere. For example, between the substrate transfer chamber 12A and the plasma pretreatment chamber 12B, the substrate 1 can be transferred through an opening provided in the partition wall 35a. The substrate transfer chamber 12A and the film formation chamber 12C have the same structure, and the substrate 1 can be transferred between the substrate transfer chamber 12A and the film formation chamber 12C.

[0126] The function of the decompression mechanism of the decompression chamber 12 will be described. The decompression mechanism of the decompression chamber 12 is configured to reduce the pressure of the atmosphere in the space in which at least the plasma pretreatment mechanism 11B or the film formation mechanism 11C of the film formation apparatus 10 is disposed to below atmospheric pressure. The decompression mechanism may be configured to reduce the pressure of each of the substrate transfer chamber 12A, the plasma pretreatment chamber 12B, and the film formation chamber 12C, which are partitioned by partition walls 35a to 35c, to below atmospheric pressure.

[0127] The configuration of the decompression mechanism of the decompression chamber 12 will be described. The decompression chamber 12 may have, for example, a vacuum pump connected to the plasma pretreatment chamber 12B. By adjusting the vacuum pump, the pressure in the plasma pretreatment chamber 12B when performing the plasma pretreatment described later can be appropriately controlled. In addition, the plasma supplied into the plasma pretreatment chamber 12B can be prevented from diffusing to other chambers by a method described later. The decompression mechanism of the decompression chamber 12 may have a vacuum pump connected to the film formation chamber 12C, similar to the vacuum pump connected to the plasma pretreatment chamber 12B. As the vacuum pump, a dry pump, a turbo molecular pump, a cryopump, a rotary pump, a diffusion pump, or the like can be used.

[0128] A substrate transport mechanism 11A for the substrate 1 of the film forming apparatus 10 according to the present embodiment will be described together with a transport path of the substrate 1. The substrate transport mechanism 11A is a mechanism arranged in the substrate transport chamber 12A for transporting the substrate 1. In the example shown in FIG. 2, the substrate transport mechanism 11A has an unwinding roller 13 to which a roll-shaped original web of the substrate 1 is attached, a winding roller 15 for winding the substrate 1, and guide rolls 14a to 14d. The substrate 1 sent out from the substrate transport mechanism 11A is then transported by a pretreatment roller 20 (described later) arranged in the plasma pretreatment chamber 12B and a film formation roller 25 (described later) arranged in the film formation chamber 12C.

[0129] Although not shown, the substrate transport mechanism 11A may further include a tension pick-up roller. By including the tension pick-up roller in the substrate transport mechanism 11A, the substrate 1 can be transported while adjusting the tension applied to the substrate 1.

[0130] (Plasma pretreatment mechanism) The plasma pretreatment mechanism 11B will be described. The plasma pretreatment mechanism 11B is a mechanism for performing plasma pretreatment on the surface of the substrate 1. The plasma pretreatment mechanism 11B shown in FIG. 2 generates plasma P and performs plasma pretreatment on the surface of the substrate 1 using the generated plasma P. When the surface of the substrate 1 is activated by plasma pretreatment, for example, hydrogen is released from the substrate resin component to generate carbon radicals. Then, functional groups such as hydroxyl groups, carboxyl groups, and ketone groups are generated by bonding with oxygen and hydrogen in the atmosphere. It is believed that the generation of such functional groups improves the adhesion between the substrate 1 and the deposition film 2. The plasma pretreatment mechanism 11B shown in FIG. 2 has a pretreatment roller 20 arranged in the plasma pretreatment chamber 12B, an electrode unit 21 facing the pretreatment roller 20, and a magnetic field forming unit 23 that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21.

[0131] The pretreatment roller 20 will be described. FIG. 3 is an enlarged view of the portion surrounded by the dashed line marked with the symbol VI in FIG. 2. Note that in FIG. 3, the power supply wiring 31 connecting the power source 32 shown in FIG. 2 and the electrode unit 21 described later, and the plasma P generated by the plasma pretreatment mechanism 11B are omitted. The pretreatment roller 20 has a rotation axis X. The pretreatment roller 20 is provided so that at least the rotation axis X is located in the plasma pretreatment chamber 12B partitioned by the partition walls 35a and 35b. The substrate 1 having a dimension in the direction of the rotation axis X is wound around the pretreatment roller 20. In the following description, the dimension of the substrate 1 in the direction of the rotation axis X is also referred to as the width of the substrate 1. The direction of the rotation axis X is also referred to as the width direction of the substrate 1.

[0132] As shown in FIG. 2, the pretreatment roller 20 may be provided so that a part of it is exposed to the substrate transport chamber 12A side. In the example shown in FIG. 2, the plasma pretreatment chamber 12B and the substrate transport chamber 12A are connected through an opening provided in the partition wall 35a, and a part of the pretreatment roller 20 is exposed to the substrate transport chamber 12A side through the opening. A gap is provided between the partition wall 35a between the substrate transport chamber 12A and the plasma pretreatment chamber 12B and the pretreatment roller 20, and the substrate 1 can be transported from the substrate transport chamber 12A to the plasma pretreatment chamber 12B through the gap. Although not shown, the pretreatment roller 20 may be provided so that the entirety thereof is located within the plasma pretreatment chamber 12B.

[0133] Although not shown, the pretreatment roller 20 may have a temperature adjustment mechanism that adjusts the surface temperature of the pretreatment roller 20. For example, the pretreatment roller 20 may have a temperature adjustment mechanism inside the pretreatment roller 20 that includes piping for circulating a temperature adjustment medium such as a refrigerant or a heat medium. The temperature adjustment mechanism adjusts the surface temperature of the pretreatment roller 20 to a target temperature within a range of, for example, −20° C. or more and 100° C. or less.

[0134] By providing the pretreatment roller 20 with a temperature adjustment mechanism, it is possible to prevent the substrate 1 from shrinking or being damaged by heat during plasma pretreatment.

[0135] The pretreatment roller 20 is made of a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the pretreatment roller 20 may be treated with a hard chrome hard coat to prevent scratches. These materials are easy to process. In addition, by using the above materials as the material for the pretreatment roller 20, the thermal conductivity of the pretreatment roller 20 itself is increased, making it easier to control the temperature of the pretreatment roller 20.

[0136] The electrode unit 21 will be described. In the example shown in FIG. 2 and FIG. 3, the electrode unit 21 has a first surface 21c facing the pretreatment roller 20 and a second surface 21d located on the opposite side of the first surface 21c. In the example shown in FIG. 2 and FIG. 3, the electrode unit 21 is a plate-shaped member, and both the first surface 21c and the second surface 21d are flat. The electrode unit 21 generates plasma between the pretreatment roller 20 by applying an AC voltage between the electrode unit 21 and the pretreatment roller 20. The electrode unit 21 preferably forms an electric field between the electrode unit 21 and the pretreatment roller 20 so that the generated plasma moves in a direction perpendicular to the surface of the substrate 1 toward the surface of the substrate 1. This allows the substrate 1 to be pretreated efficiently.

[0137] The number of electrode portions 21 is preferably 2 or more. The two or more electrode portions 21 are preferably arranged along the transport direction of the substrate 1. In the example shown in Fig. 2 and Fig. 3, an example is shown in which the film forming apparatus 10 has two electrode portions 21. In addition, the number of electrode portions 21 is, for example, 12 or less.

[0138] The effect of two or more electrode sections 21 arranged along the transport direction of the substrate 1 will be described. As described above, plasma is generated between the electrode section 21 and the pretreatment roller 20. The region in which plasma is generated expands as the dimension of the electrode section 21 in the transport direction increases. On the other hand, when the electrode section 21 is a flat plate-like member, the larger the dimension of the electrode section 21 in the transport direction, the greater the distance from the end of the first surface 21c, which is the surface of the electrode section 21 facing the pretreatment roller 20, to the pretreatment roller 20 in the transport direction, which reduces the processing ability by plasma.

[0139] In the film forming apparatus 10, two or more electrode units 21 are arranged along the transport direction of the substrate 1. Therefore, even if the dimension of the electrode unit 21 in the transport direction of the substrate 1 is small, plasma can be generated over a wide range in the transport direction. Furthermore, by reducing the dimension of the electrode unit 21, the distance from the end of the first surface 21c of the electrode unit 21 to the pretreatment roller 20 in the transport direction can be reduced, and plasma can be generated uniformly in the transport direction.

[0140] As shown in FIG. 2 and FIG. 3, the electrode unit 21 has a first end 21e and a second end 21f located on the first surface 21c of the electrode unit 21. The first end 21e is an end on the upstream side in the conveying direction of the substrate 1, and the second end 21f is an end on the downstream side in the conveying direction of the substrate 1. As described above, by reducing the dimension of the electrode unit 21 in the conveying direction of the substrate 1, the distance from the first end 21e and the second end 21f of the electrode unit 21 to the pre-treatment roller 20 in the conveying direction can be reduced. The dimension of the electrode unit 21 in the conveying direction of the substrate 1 corresponds to the angle θ shown in FIG. 3. The angle θ is the angle formed by a straight line passing through the first end 21e and the rotation axis X and a straight line passing through the second end 21f and the rotation axis X. The angle θ is preferably 20° or more and 90° or less, more preferably 60° or less, and even more preferably 45° or less. When the angle θ is within the above range, plasma can be generated uniformly in the transport direction between the electrode unit 21 and the pretreatment roller 20 when the first surface 21c of the electrode unit 21 is a flat surface.

[0141] There are no particular limitations on the material of the electrode portion 21 as long as it is conductive. Specifically, aluminum, copper, and stainless steel are preferably used as the material of the electrode portion 21.

[0142] The thickness L3 of the electrode unit 21 when viewed in a direction perpendicular to the first surface 21c of the electrode unit 21 is not particularly limited, but is, for example, 15 mm or less. When the thickness of the electrode unit 21 is the above value, a magnetic field can be effectively formed between the pre-treatment roller 20 and the electrode unit 21 by the magnetic field forming unit 23. The thickness L3 of the electrode unit 21 is, for example, 3 mm or more.

[0143] The magnetic field forming unit 23 will be described. As shown in Figs. 2 and 3, the magnetic field forming unit 23 is provided on the side of the electrode unit 21 opposite to the side facing the pretreatment roller 20. The magnetic field forming unit 23 is a member that forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field between the pretreatment roller 20 and the electrode unit 21 contributes to the generation of higher density plasma, for example, when plasma is generated using the plasma pretreatment mechanism 11B. The magnetic field forming unit 23 shown in Figs. 2 and 3 has a first magnet 231 and a second magnet 232 provided on the second surface 21d of the electrode unit 21.

[0144] The number of the magnetic field forming units 23 is preferably 2 or more. When the plasma pretreatment mechanism 11B has two or more electrode units 21 and two or more magnetic field forming units 23, each of the two or more magnetic field forming units 23 is preferably provided on the side of each of the two or more electrode units 21 opposite to the side facing the pretreatment roller 20. In the example shown in Figures 2 and 3, each of the two magnetic field forming units 23 is provided on the second surface 21d of each of the two electrode units 21.

[0145] The structure of the first magnet 231 and the second magnet 232 in the normal direction of the second surface 21d of the electrode unit 21 will be described. As shown in FIG. 2 and FIG. 3, the first magnet 231 and the second magnet 232 each have an N pole and an S pole. The symbol N shown in FIG. 2 and FIG. 3 indicates the N pole of the first magnet 231 or the second magnet 232. Also, the symbol S shown in FIG. 2 and FIG. 3 indicates the S pole of the first magnet 231 or the second magnet 232. One of the N pole or S pole of the first magnet 231 is located closer to the substrate 1 than the other. Also, the other of the N pole or S pole of the second magnet 232 is located closer to the substrate 1 than the other. In the example shown in FIG. 2 and FIG. 3, the N pole of the first magnet 231 is located closer to the substrate 1 than the S pole of the first magnet 231, and the S pole of the second magnet 232 is located closer to the substrate 1 than the N pole of the second magnet. Although not shown, the south pole of first magnet 231 may be located closer to substrate 1 than the north pole of first magnet 231, and the north pole of second magnet 232 may be located closer to substrate 1 than the south pole of second magnet 232.

[0146] Next, the structures of the first magnet 231 and the second magnet 232 in the planar direction of the second surface 21d of the electrode unit 21 will be described. Fig. 4 is a plan view of the electrode unit 21 and the magnetic field forming unit 23 shown in Fig. 2, viewed from the magnetic field forming unit 23 side. Fig. 5 is a cross-sectional view showing a cross section taken along line VIII-VIII in Fig. 4. In Fig. 4, direction D1 is the direction in which the rotation axis X of the pre-treatment roller 20 extends.

[0147] As shown in Figures 4 and 5, the first magnet 231 has a first axial portion 231c. As shown in Figure 4, the first axial portion 231c extends along the direction D1, i.e., along the rotation axis X of the pre-treatment roller 20. The first magnet 231 provided in one electrode unit 21 may have one first axial portion 231c, or may have two or more first axial portions 231c. In the example shown in Figure 4, the first magnet 231 provided in one electrode unit 21 has one first axial portion 231c.

[0148] 4 and 5, the second magnet 232 has a second axial portion 232c. As shown in Fig. 4, the second axial portion 232c also extends along the direction D1, i.e., along the rotation axis X, similar to the first axial portion 231c.

[0149] Since both the first magnet 231 and the second magnet 232 include a portion extending along the rotation axis X, it is possible to increase the uniformity of the strength of the magnetic field formed around the substrate 1 in the width direction of the substrate 1. This makes it possible to increase the uniformity of the distribution density of the plasma formed around the substrate 1 in the width direction of the substrate 1.

[0150] The second magnet 232 provided on one electrode unit 21 may have one second axial portion 232c, or may have two or more second axial portions 232c. In the example shown in Fig. 4 and Fig. 5, the second magnet 232 provided on one electrode unit 21 has two second axial portions 232c. The two second axial portions 232c may be positioned so as to sandwich the first axial portion 231c in a direction D2 perpendicular to the rotation axis X in the planar direction of the second surface 21d of the electrode unit 21.

[0151] 5, the dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 are not particularly limited. In addition, the ratio of the dimension L4 of the first axial portion 231c to the dimension L5 of the second axial portion 232c in the transport direction of the base material 1 is not particularly limited. The dimension L4 of the first axial portion 231c and the dimension L5 of the second axial portion 232c may be equal, or the dimension L4 of the first axial portion 231c may be larger than the dimension L5 of the second axial portion 232c.

[0152] The distance L6 between the first axial portion 231c and the second axial portion 232c in the direction D2 is set so that a magnetic field generated by the first axial portion 231c and the second axial portion 232c is formed between the pre-treatment roller 20 and the electrode portion 21.

[0153] The second magnet 232 may surround the first magnet 231 when the magnetic field generating unit 23 is viewed along the normal direction of the second surface 21d of the electrode unit 21. For example, as shown in Fig. 4, the second magnet 232 may have two second axial portions 232c as well as two connection portions 232d provided to connect the two second axial portions 232c.

[0154] Examples of the types of magnets used as the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, include permanent magnets such as ferrite magnets and rare earth magnets such as neodymium and samarium cobalt (samarium cobalt). Also, an electromagnet can be used as the magnetic field forming unit 23.

[0155] The magnetic flux density of the magnets of the magnetic field forming unit 23, such as the first magnet 231 and the second magnet 232, is, for example, 100 Gauss or more and 10,000 Gauss or less. If the magnetic flux density is 100 Gauss or more, a sufficiently strong magnetic field can be formed between the pretreatment roller 20 and the electrode unit 21, thereby generating plasma with a sufficiently high density, and a good pretreatment surface can be formed at high speed. On the other hand, in order to increase the magnetic flux density on the surface of the substrate 1 to more than 10,000 Gauss, an expensive magnet or magnetic field generating mechanism is required.

[0156] Although not shown, the plasma pretreatment mechanism 11B may have a plasma raw material gas supply unit. The plasma raw material gas supply unit supplies a gas serving as a raw material for plasma into the plasma pretreatment chamber 12B. The configuration of the plasma raw material gas supply unit is not particularly limited. For example, the plasma raw material gas supply unit is provided on the wall surface of the plasma pretreatment chamber 12B and includes a hole for ejecting the gas serving as a raw material for plasma. The plasma raw material gas supply unit may have a nozzle for ejecting the plasma raw material gas at a position closer to the substrate 1 than the wall surface of the plasma pretreatment chamber 12B. The plasma raw material gas supplied by the plasma raw material gas supply unit may be, for example, an inert gas such as argon, an active gas such as oxygen, nitrogen, carbon dioxide, or ethylene, or a mixed gas of these gases. As the plasma raw material gas, one kind of inert gas may be used alone, one kind of active gas may be used alone, or a mixed gas of two or more kinds of gases contained in the inert gas or active gas may be used. As the plasma raw material gas, a mixed gas of an inert gas such as argon and an active gas may be used. As an example, the plasma raw material gas supply unit supplies a mixed gas of argon (Ar) and oxygen (O2).

[0157] The plasma pretreatment mechanism 11B has a plasma density of, for example, 100 W·sec / m 2 More than 8000W sec / m 2 The following plasma is supplied between the pretreatment roller 20 and the electrode unit 21.

[0158] 2, the plasma pretreatment mechanism 11B is disposed in a plasma pretreatment chamber 12B separated by a partition from the substrate transport chamber 12A and the film formation chamber 12C. By separating the plasma pretreatment chamber 12B from other regions such as the substrate transport chamber 12A and the film formation chamber 12C, it becomes easier to adjust the atmosphere in the plasma pretreatment chamber 12B independently. This makes it easier to control the plasma raw material gas concentration in the space where the pretreatment roller 20 and the electrode unit 21 face each other, improving the productivity of the laminated film.

[0159] (Film forming mechanism) Next, the film formation mechanism 11C will be described. In the example shown in Fig. 2, the film formation mechanism 11C includes a film formation roller 25 and an evaporation mechanism 24 disposed in a film formation chamber 12C.

[0160] The film-forming roller 25 will be described below. The film-forming roller 25 is a roller that wraps around and transports the substrate 1 with the treated surface of the substrate 1 that has been pretreated in the plasma pretreatment mechanism 11B facing outward.

[0161] The material of the film-forming roller 25 will be described. The film-forming roller 25 is preferably formed from a material containing at least one of stainless steel, iron, copper, and chromium. The surface of the film-forming roller 25 may be subjected to a hard chrome hard coat treatment or the like to prevent scratches. These materials are easy to process. In addition, by using the above-mentioned materials as the material of the film-forming roller 25, the thermal conductivity of the film-forming roller 25 itself is increased, so that the temperature controllability is excellent when performing temperature control. The surface average roughness Ra of the film-forming roller 25 is, for example, 0.1 μm or more and 10 μm or less.

[0162] Although not shown, the film-forming roller 25 may have a temperature adjustment mechanism for adjusting the temperature of the surface of the film-forming roller 25. The temperature adjustment mechanism has, for example, a circulation path for circulating a cooling medium or a heat source medium inside the film-forming roller 25. The cooling medium (coolant) is, for example, an ethylene glycol aqueous solution, and the heat source medium (heat medium) is, for example, silicone oil. The temperature adjustment mechanism may have a heater installed at a position facing the film-forming roller 25. When the film-forming mechanism 11C forms a film by a deposition method, the temperature adjustment mechanism preferably adjusts the surface temperature of the film-forming roller 25 to a target temperature within a range of -20°C to 200°C in terms of restrictions on the heat resistance of related mechanical parts and versatility. By having the temperature adjustment mechanism in the film-forming roller 25, it is possible to suppress the temperature fluctuation of the substrate 1 caused by the heat generated during film formation.

[0163] The evaporation mechanism 24 will be described. FIG. 6 is an enlarged view of the portion surrounded by the dashed line marked with the symbol IX in FIG. 2, showing a specific form of the evaporation mechanism 24 that was omitted in FIG. 5, and showing an evaporation material supply unit 61 that supplies an evaporation material that was omitted in FIG. 2. Note that the decompression chamber 12 and the partition walls 35b and 35c are omitted in FIG. 6. The evaporation mechanism 24 is a mechanism that evaporates an evaporation material containing aluminum. The evaporated evaporation material adheres to the substrate 1, so that an evaporation film containing aluminum is formed on the surface of the substrate 1. The evaporation mechanism 24 in this embodiment employs a resistance heating type. In the example shown in FIG. 6, the evaporation mechanism 24 has a boat 24b. In this embodiment, the boat 24b has a power source (not shown) and a resistor (not shown) electrically connected to the power source. A plurality of boats 24b may be arranged in the width direction of the substrate 1.

[0164] As shown in Fig. 6, the film formation mechanism 11C may have a deposition material supply unit 61 that supplies a deposition material to the evaporation mechanism 24. Fig. 6 shows an example in which the deposition material supply unit 61 continuously feeds out an aluminum metal wire.

[0165] Although not shown, the film formation mechanism 11C has a gas supply mechanism. The gas supply mechanism is a mechanism that supplies gas between the evaporation mechanism 24 and the film formation roller 25. The gas supply mechanism supplies at least oxygen gas. The oxygen gas reacts with or bonds with an evaporation material such as aluminum that has evaporated from the evaporation mechanism 24 and is heading toward the substrate 1 on the film formation roller 25. This allows a vapor deposition film containing aluminum oxide to be formed on the surface of the substrate 1.

[0166] The film forming mechanism 11C also includes a plasma supply mechanism 50 that supplies plasma between the surface of the substrate 1 and the evaporation mechanism 24. In the example shown in FIG. 2 and FIG. 6, the plasma supply mechanism 50 has a hollow cathode 51. In this embodiment, the hollow cathode 51 is a cathode having a hollow portion that is partially open. The hollow cathode 51 can generate plasma in the hollow portion. In the example shown in FIG. 6, the hollow cathode 51 is provided so that the opening of the hollow portion of the hollow cathode 51 is located diagonally above the boat 24b. Although not shown, the plasma supply mechanism 50 according to this embodiment has an anode facing the opening, which draws out plasma from the opening of the hollow portion of the hollow cathode 51. The plasma supply mechanism 50 according to this embodiment can generate strong plasma between the surface of the substrate 1 and the evaporation mechanism 24 by generating plasma in the hollow portion of the hollow cathode 51 and drawing the plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the opposing anode. The position of the opposing anodes is not particularly limited as long as the opposing anodes can draw out plasma from the opening of the cavity of the hollow cathode 51 and supply plasma between the surface of the substrate 1 and the evaporation mechanism 24. In this embodiment, a case where the opposing anodes are arranged on both sides of the boat 24b in the width direction of the substrate 1 will be described. In this case, the film formation mechanism 11C has a plurality of boats 24b and a plurality of opposing anodes, and the plurality of boats 24b and the plurality of opposing anodes may be arranged alternately in the width direction of the substrate 1. Although not shown, the plasma supply mechanism 50 may have a raw material supply device that supplies plasma raw material gas at least into the cavity of the hollow cathode 51. As the plasma raw material gas supplied by the raw material supply device, for example, a gas similar to the gas that can be used as the plasma raw material gas supplied by the plasma raw material gas supply unit of the plasma pretreatment mechanism 11B can be used.

[0167] By performing plasma assist during deposition by supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 using the plasma supply mechanism 50, the aluminum evaporated in the evaporation mechanism 24 and the oxygen gas can be activated, and the reaction or bonding between the aluminum and the oxygen gas can be promoted. This can increase the proportion of aluminum present as aluminum oxide in the evaporated film 2 formed on the surface of the substrate 1, and stabilize the properties of the evaporated film 2.

[0168] Although not shown, the film forming apparatus 10 may include a substrate charge removal unit that performs post-processing to remove charge generated on the substrate 1 due to film formation by the film formation mechanism 11C, in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1. The substrate charge removal unit may be provided so as to remove charge from one side of the substrate 1, or may be provided so as to remove charge from both sides of the substrate 1.

[0169] The device used as the substrate charge removal section for performing post-treatment on the substrate 1 is not particularly limited, but for example, a plasma discharge device, an electron beam irradiation device, an ultraviolet ray irradiation device, a static elimination bar, a glow discharge device, a corona treatment device, etc. can be used.

[0170] When performing post-treatment by forming a discharge using a plasma treatment device or a glow discharge device, a discharge gas such as argon, oxygen, nitrogen, helium, or a mixture of these gases is supplied near the substrate 1, and post-treatment can be performed using any discharge method such as alternating current (AC) plasma, direct current (DC) plasma, arc discharge, microwave, surface wave plasma, etc. In a reduced pressure environment, it is most preferable to perform post-treatment using a plasma discharge device.

[0171] The substrate charge removal section is provided in a portion of the substrate transport chamber 12A that is located downstream of the film formation chamber 12C in the transport direction of the substrate 1, and the charge on the substrate 1 is removed, so that the substrate 1 can be transported by quickly separating it from the film formation roller 25 at a predetermined position. This enables stable substrate transport, prevents damage to the substrate 1 or deterioration in quality due to charging, and improves post-processing suitability by improving the wettability of the front and back surfaces of the substrate.

[0172] (power supply) In the example shown in FIG. 2, the film forming apparatus 10 further includes a power source 32 electrically connected to the pretreatment roller 20 and the electrode unit 21. In the example shown in FIG. 5, the power source 32 is electrically connected to the pretreatment roller 20 and the electrode unit 21 via the power supply wiring 31. The power source 32 is, for example, an AC power source. When the power source 32 is an AC power source, the power source 32 can apply an AC voltage having a frequency of, for example, 20 kHz or more and 500 kHz or less between the pretreatment roller 20 and the electrode unit 21. The input power that can be applied by the power source 32 (power that can be applied per 1 m width of the electrode unit 21 in the width direction of the substrate 1) is not particularly limited, but is, for example, 0.5 kW / m or more and 20 kW / m or less. The pretreatment roller 20 may be installed at an electrically earth level or at an electrically floating level.

[0173] (Barrier film manufacturing method) Next, a method for manufacturing the barrier film shown in FIG. 1 using the above-mentioned film forming apparatus 10 will be described. First, a film forming method for forming a vapor-deposited film 2 on the surface of the substrate 1 will be described. In film formation using the film forming apparatus 10, a plasma pretreatment step of performing plasma pretreatment on the surface of the substrate 1 using the plasma pretreatment mechanism 11B and a film formation step of forming a vapor-deposited film on the surface of the substrate 1 using the film formation mechanism 11C are performed while the substrate 1 is transported along the above-mentioned transport path of the substrate 1. The transport speed of the substrate 1 is preferably 200 m / min or more, and more preferably 400 m / min or more and 1000 m / min or less.

[0174] (Plasma pretreatment process) The plasma pretreatment step is carried out, for example, by the following method. First, plasma raw material gas is supplied into the plasma pretreatment chamber 12B. Next, the above-mentioned AC voltage is applied between the pretreatment roller 20 and the electrode unit 21. When applying the AC voltage, input power control or impedance control may be performed.

[0175] The plasma raw material gas supplied in the pretreatment is oxygen alone or a mixture of oxygen gas and an inert gas, which is supplied from a gas reservoir while measuring the flow rate of the gas through a flow rate controller. The inert gas may be one or a mixture of two or more gases selected from the group consisting of argon, helium, and nitrogen.

[0176] In the plasma treatment, the mixing ratio of oxygen gas to the inert gas, that is, oxygen gas / inert gas, is preferably 6 / 1 to 1 / 1, and more preferably 5 / 2 to 3 / 2.5.

[0177] By setting the mixing ratio to 6 / 1 to 1 / 1, the energy required for forming the evaporated aluminum film on the resin substrate is increased, and by setting the ratio to 5 / 2 to 3 / 2, the degree of oxidation of the evaporated aluminum oxide film is increased, ensuring adhesion between the evaporated aluminum oxide film and the substrate.

[0178] Application of the AC voltage generates plasma simultaneously with glow discharge, and plasma P is densified between pretreatment roller 20 and magnetic field forming unit 23. In this manner, plasma P can be supplied between pretreatment roller 20 and magnetic field forming unit 23. This plasma P can be used to perform plasma (ion) pretreatment on the surface of substrate 1.

[0179] Plasma intensity per unit area in plasma processing is 50 W·sec / m 2 More than 8000W sec / m 2 Less than 50W sec / m 2 Below this, no effect of plasma pretreatment was observed, and below 8000W·sec / m 2Above this level, the resin substrate tends to deteriorate due to the plasma, such as wear, damage, discoloration, and burning. In particular, the plasma intensity for plasma pretreatment to form an aluminum oxide layer should be 100 W·sec / m 2 More than 1000W sec / m 2 The following is preferred:

[0180] The pressure in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 is reduced to below atmospheric pressure by decompression chamber 12. In this case, the pressure in plasma pretreatment chamber 12B is adjusted, for example, so that a glow discharge can be generated between pretreatment roller 20 and electrode unit 21 by application of an AC voltage. The pressure in plasma pretreatment chamber 12B when an AC voltage is applied between pretreatment roller 20 and electrode unit 21 can be set and maintained at about 0.1 Pa or more and 100 Pa or less, and is particularly preferably 1 Pa or more and 20 Pa or less.

[0181] The function of the magnetic field forming unit 23 in the plasma pretreatment step will now be described. The magnetic field forming unit 23 forms a magnetic field between the pretreatment roller 20 and the electrode unit 21. The magnetic field can act to capture and accelerate electrons present between the pretreatment roller 20 and the electrode unit 21. As a result, in the region where the magnetic field is formed, it is possible to increase the frequency of collisions between the electrons and the plasma raw material gas, increase the density of the plasma, and localize it, thereby improving the efficiency of the plasma pretreatment.

[0182] (Film forming process) In the film formation step, a film is formed using film formation mechanism 11C on the surface of substrate 1. As an example of the film formation step, a case will be described in which an aluminum oxide vapor deposition film is formed using film formation mechanism 11C having an evaporation mechanism 24 shown in FIG.

[0183] First, a deposition material containing aluminum is supplied into the boat 24b of the evaporation mechanism 24 so as to face the deposition roller 25. An aluminum metal wire can be used as the deposition material. In the example shown in Fig. 6, the deposition material is supplied to the boat 24b by continuously feeding the aluminum metal wire into the boat 24b using a deposition material supply unit 61.

[0184] The aluminum is evaporated in the boat 24b by heating. For convenience, FIG. 6 shows evaporated aluminum vapor 63. The oxygen gas for oxidizing the aluminum may be supplied as oxygen alone or as a mixed gas with an inert gas such as argon, but by controlling the amount of oxygen, both barrier properties and transparency can be achieved. The pressure at this time is preferably 0.05 Pa or more and 8.00 Pa or less.

[0185] Furthermore, a method for supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24 by the plasma supply mechanism 50, i.e., plasma assist during deposition, will be described. In this embodiment, plasma is generated within the cavity of the hollow cathode 51 of the plasma supply mechanism 50. Next, a discharge is generated between the hollow cathode 51 and the opposing anode, and the plasma within the cavity of the hollow cathode 51 is drawn between the surface of the substrate 1 and the evaporation mechanism 24.

[0186] In this embodiment, the discharge generated between hollow cathode 51 and the opposing anode is an arc discharge. The arc discharge means a discharge with a current value of, for example, 10 A or more.

[0187] By evaporating aluminum while supplying plasma between the surface of the substrate 1 and the evaporation mechanism 24, plasma is supplied to the aluminum vapor 63. Supplying plasma can promote the reaction or bonding between the aluminum vapor 63 and oxygen gas. This allows the aluminum vapor 63 to be oxidized before it reaches the surface of the substrate 1. The evaporated and oxidized aluminum adheres to the substrate 1, forming an aluminum oxide vapor deposition film on the surface of the substrate 1, and the barrier film shown in FIG. 1 can be manufactured.

[0188] The plasma raw material gas supplied by the plasma supply mechanism 50 is preferably argon gas.

[0189] In this embodiment, a plasma pretreatment step is performed before the film formation step, in which plasma is supplied to the surface of the substrate 1. In the plasma pretreatment step, an AC voltage is applied between the electrode unit 21 and the pretreatment roller 20. In addition, a magnetic field is generated in the space between the electrode unit 21 and the pretreatment roller 20 by using the magnetic field forming unit 23 located on the side of the surface of the electrode unit 21 opposite to the surface facing the pretreatment roller 20. Therefore, plasma can be efficiently generated in the space between the electrode unit 21 and the pretreatment roller 20, and the plasma can be made to perpendicularly enter the surface of the substrate 1 wound around the pretreatment roller 20. Therefore, the adhesion between the film formed in the film formation step and the substrate 1 can be improved.

[0190] (Aging treatment after film formation process) The barrier film roll that has been subjected to the above-mentioned film-forming process is then subjected to an aging treatment (heating treatment) for a predetermined period of time, which promotes the introduction of hydroxyl groups into the vapor-deposited aluminum oxide film, resulting in a vapor-deposited film with excellent oxygen permeability and water vapor permeability.

[0191] The aging temperature is preferably 50° C. or higher and 60° C. or lower. The lower limit of the aging time is 24 hours (1 day) or higher, more preferably 48 hours (2 days) or higher. The upper limit is 144 hours (6 days) or lower, more preferably 96 hours (4 days) or lower. The aging humidity is not particularly limited, but does not need to be high, and may be normal relative humidity of 40% or higher and 70% or lower.

[0192] (Coating layer formation process) The coating layer 3 can be produced by the following method. First, the above metal alkoxide, water-soluble polymer, silane coupling agent added as necessary, sol-gel catalyst, acid, and organic solvent such as water as a solvent, methyl alcohol, ethyl alcohol, isopropanol, etc., are mixed to prepare a barrier coating agent. Next, the above barrier coating agent is applied on the aluminum oxide vapor deposition film by a conventional method and dried. This drying step further advances polycondensation of silanols generated from the above metal alkoxide and silane coupling agent to form a coating film. The drying conditions include a temperature of 20 to 200°C and below the melting point of the plastic substrate, preferably a temperature in the range of 50 to 180°C, and a heat treatment for 3 seconds to 10 minutes. This allows the coating layer 3 made of the above barrier coating agent to be formed on the aluminum oxide vapor deposition film. The above coating operation may be further repeated on the first coating film to form a plurality of coating films consisting of two or more layers.

[0193] The barrier film roll that has been subjected to the above-mentioned coating layer forming process is then subjected to an aging treatment (heating treatment) for a predetermined period of time, which allows the coating layer to condense appropriately, resulting in a barrier film whose barrier properties are unlikely to deteriorate after a retort test.

[0194] The lower limit of the aging temperature after the coating layer forming step is preferably 40°C or higher, more preferably 50°C or higher. The upper limit is preferably 100°C or lower, more preferably 70°C or lower. The lower limit of the aging time is 24 hours (1 day) or higher, more preferably 48 hours (2 days) or higher. The upper limit is 144 hours (6 days) or lower, more preferably 96 hours (4 days) or lower. The aging humidity is not particularly limited, but does not need to be high, and may be normal relative humidity of 40% or higher and 70% or lower.

[0195] (Film forming process 2) An aluminum oxide film may be further deposited on the coating layer under the same conditions as those for the above-mentioned film deposition step and aging treatment.

[0196] (Coating layer formation step 2) A coating layer may be further formed on the aluminum oxide vapor-deposited film vapor-deposited through the film-forming step 2. The film can be formed under the same conditions as in the coating layer forming step.

[0197] (Laminate) FIG. 7 is a cross-sectional view showing an example of a laminate using the barrier film according to the present embodiment. This laminate 100 is a laminate using the barrier film 100A of FIG. 1. That is, the barrier film 100A is composed of a first polypropylene base material 110, a foundation layer 115, a vapor deposition film 120, and a coating layer 130 having a barrier property. One surface of the barrier film on the first polypropylene base material 110 side is laminated with a sealant layer 150 via a first adhesive layer 161, and the other surface of the barrier film on the coating layer 130 side is laminated with a second polypropylene base material 140 via an adhesive layer 162. That is, it has a three-layer film configuration with the barrier film as an intermediate layer, that is, the second polypropylene base material 140 / second adhesive layer 162 / barrier film / first adhesive layer 161 / sealant layer 150. The configuration other than the barrier film A will be described below.

[0198] [Adhesive layer] The surface of the barrier film facing the first polypropylene base material 110 is laminated to the sealant layer 150 via a first adhesive layer 161, and the surface of the barrier film facing the covering layer 130 is laminated to the second polypropylene base material 140 via an adhesive layer 162. This improves the adhesion between the barrier film and the sealant layer, and between the first polypropylene base material and the second base material, and suppresses the deterioration of the barrier properties during heat sterilization treatment such as retort or boiling.

[0199] The first adhesive layer 161 and the second adhesive layer 162 may be a one-component curing adhesive, a two-component curing adhesive, or a non-curing adhesive. The adhesive may be a solventless adhesive or a solvent-based adhesive suitable for dry lamination.

[0200] Examples of solvent-free adhesives, i.e., non-solvent lamination adhesives, include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives. Among these, urethane adhesives are preferred, and two-liquid curing urethane adhesives are more preferred.

[0201] Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, olefin-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and urethane-based adhesives. Among these, urethane-based adhesives are preferred, and two-liquid curing urethane-based adhesives are more preferred.

[0202] The thickness of the adhesive layer is, for example, 0.1 μm or more and 10 μm or less, preferably 0.2 μm or more and 8 μm or less, and more preferably 0.5 μm or more and 6 μm or less.

[0203] [Second polypropylene base material] The second polypropylene base material 140 is laminated to the surface of the barrier film facing the covering layer 30 via a second adhesive layer 162. Here, the second polypropylene base material may be the same as the first polypropylene base material 110, and therefore a description thereof will be omitted.

[0204] In the case of a three-layer structure as shown in Figure 7, the printed layer (not shown) may be formed on the surface of the outermost layer of the second polypropylene base material 140, or on the surface of the second polypropylene base material 140 on the second adhesive layer 162 side.

[0205] [Sealant layer] The sealant layer 150 contains a resin material that can be fused to each other by heat. Examples of the resin material that can be fused to each other by heat include polyolefins, and specific examples of such resin materials include polyethylenes such as low-density polyethylene, linear low-density polyethylene, and medium-density polyethylene, polypropylene, polybutene, methylpentene polymers, and cyclic olefin copolymers.

[0206] The sealant layer is preferably made of polypropylene. This allows the three-layer film to be made entirely of polypropylene, making it possible to make the packaging material mono-material. After collecting used packaging materials, there is no need to separate the base material and the sealant layer, improving the recyclability of the packaging material. By making the sealant layer of polypropylene, the oil resistance can also be improved, making it possible to make the sealant layer resistant to heat sterilization treatment.

[0207] The content of polypropylene in the sealant layer is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more, which can improve, for example, the recyclability of packaging materials.

[0208] When the sealant layer is made of polypropylene, the content of polypropylene in the total amount of resin materials contained in the laminate is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 88% by mass or more, and particularly preferably 90% by mass or more. This allows, for example, the laminate to be used to produce a mono-material packaging material, improving the recyclability of the packaging material.

[0209] Examples of polypropylene include propylene homopolymers, propylene random copolymers such as propylene-α-olefin random copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. The details of the α-olefins are as described above. From the viewpoint of heat sealability, the density of the polypropylene is, for example, 0.88 g / cm3 or more and 0.92 g / cm3 or less. The density is measured in accordance with JIS K7112, particularly the D method (density gradient tube method, 23°C). From the viewpoint of reducing the environmental load, biomass-derived polypropylene and / or recycled polypropylene may be used.

[0210] The sealant layer may contain an additive. Examples of the additive include a crosslinking agent, an antioxidant, an antiblocking agent, a slip agent, an ultraviolet absorber, a light stabilizer, a filler, a reinforcing agent, a lubricant, an antistatic agent, a pigment, and a modifying resin. For example, the sealant layer may contain an antistatic agent. This can suppress the generation of static electricity on the surface of the laminate, and can suppress, for example, adhesion between laminates.

[0211] The sealant layer may have a single-layer structure or a multi-layer structure. The thickness of the sealant layer is preferably 10 μm or more and 200 μm or less, more preferably 20 μm or more and 150 μm or less. When the thickness is equal to or more than the lower limit, for example, the lamination strength of the packaging material including the laminate can be improved. When the thickness is equal to or less than the upper limit, for example, the processability of the laminate can be improved. When a pouch (particularly a retort pouch) is produced from the laminate, the thickness of the sealant layer is more preferably 30 μm or more and 100 μm or less.

[0212] From the viewpoint of heat sealability, the sealant layer is preferably an unstretched resin film, more preferably an unstretched polypropylene film. The resin film can be produced, for example, by using a casting method, a T-die method, an inflation method, or the like. The sealant layer may be laminated via an adhesive layer as in the present embodiment, or may be formed by melt-extruding a resin material that can be fused to each other by heat onto a barrier film.

[0213] [Other lamination examples] 8 shows an example in which the covering layer 130 of the barrier film A is laminated to the sealant layer 150 via a first adhesive layer 161. Thus, in the present invention, the laminate is not limited to a three-layer film structure, and may be a two-layer structure.

[0214] [Packaging products] The laminate can be used as a packaging product such as a packaging bag for containing contents such as food by forming the laminate into a bag shape with the sealant layer on the inside. The laminate of the present invention is a heat sterilized laminate used for a packaging bag for containing retort food or boiled food.

[0215] The heat sterilization treatment includes not only retort treatment but also boiling treatment. The boiling treatment means heat sterilization at 60 to 100° C. for 10 to 60 minutes, for example.

[0216] Retort treatment means a heat and pressure sterilization treatment at 100 to 140°C. The F value, which is a concept representing the integral value of the load heat amount, is 4 or more, more specifically, a heat and pressure sterilization treatment at 121°C for 3 minutes or more, or a heat and pressure sterilization treatment at 120°C for 4 minutes or more as stipulated in the Food Sanitation Act is preferable. More specifically, 120°C for 30 to 60 minutes is most common, but semi-retort at 105 to 115°C for 30 to 60 minutes and high retort (HTST) at 130 to 140°C for 30 to 60 minutes are also acceptable.

[0217] [Complex elastic modulus and indentation hardness of coating layer] In the present invention, the composite elastic modulus and indentation hardness after lamination and the above-mentioned heat sterilization treatment are measured by nanoindentation from a cross section of the coating layer of the laminate, and are 5.0 GPa to 8.5 GPa, and the indentation hardness is 0.9 GPa to 1.7 GPa. When the composite elastic modulus and indentation hardness are within this range, the deterioration of the barrier property of the laminate can be suppressed not only after boiling treatment but also after retort treatment.

[0218] It is more preferable that the composite elastic modulus is 6.0 GPa or more and 8.5 GPa or less and the indentation hardness is 1.0 GPa or more and 1.5 GPa or less, and deterioration of the barrier property can be suppressed even after high-temperature retort treatment of the laminate.

[0219] The indentation hardness of the coating layer is calculated by the following formula (1): Furthermore, the composite elastic modulus of the coating layer is calculated by the following formula (2). Indentation hardness = Pmax / A (1)

number

[0220] Where: Pmax: Maximum load (unit: μN) A: Contact projection area at maximum depth (unit: μm 2 ) S: Contact stiffness It is.

[0221] The composite modulus and indentation hardness of the coating layer of the laminate after heat sterilization are measured by embedding the laminate after heat sterilization in epoxy resin or the like, and processing it with a microtome to expose the cross section of the coating layer. This allows measurement by nanoindentation from the "cross section" of the coating layer of the laminate. This method allows measurement of the composite modulus and indentation hardness of the coating layer without peeling the laminate to expose the coating layer. The cross section is obtained by cutting in the thickness direction perpendicular to the main surface of the film. The cross section was prepared by preparing a block in which the film was embedded in an embedding resin, and cutting the block using a commercially available rotary microtome at room temperature (23°C). Finishing was performed with a diamond knife.

[0222] The indentation hardness and composite modulus of the cross section of the coating layer are measured by the nanoindentation method. First, the indenter is placed on the cross section of the coating layer, and the indenter is pressed from the cross section to a load of 15 μN over 10 seconds, and the state is maintained for 5 seconds. The indenter is pressed into the vicinity of the center in the thickness direction of the coating layer among the exposed cross sections of the coating layer. Then, the load is removed over 10 seconds. This provides the maximum load Pmax, the contact projected area A at the maximum depth, and the load-displacement curve. The measurement is performed under an environment of 50% relative humidity and 23°C unless otherwise specified. The measurement is performed at five or more points on the same cross section, and the indentation hardness and composite modulus are each described as the arithmetic average value of the values ​​of five points measured with good reproducibility. Further detailed measurement conditions are described in the examples.

[0223] When the laminate is heat sterilized, the coating layer needs to have a certain degree of hardness to prevent destruction of the vapor-deposited film due to thermal shrinkage of the OPP substrate during heat sterilization. On the other hand, during lamination processing of the packaging material, the OPP substrate is stretched by tension, which also causes destruction of the vapor-deposited film and reduces the barrier properties, but this can be prevented by imparting appropriate flexibility to the coating layer.

[0224] The inventors have discovered a range of elastic modulus and indentation hardness suitable for heat sterilization treatment applications such as retort treatment for the coating layer that constitutes a monomaterial packaging material, which is a laminate of polypropylene films, and have found a laminate that can suppress a decrease in barrier property even after "heat sterilization treatment" of "lamination."

[0225] As a result, the oxygen permeability of the laminate after heat sterilization treatment, in accordance with JIS K 7126-2, at 23°C and 90% RH, was 10.0 cc / (m 2 ·day·atm) or less, preferably 5.0cc / (m 2 ·day·atm) or less, and especially preferably 2.0cc / (m 2 ·day·atm) or less, most preferably 1.0cc / (m 2 ·day·atm) or less. In addition, the water vapor transmission rate at 40°C and 100% RH according to JIS K 7129 B method after heat sterilization is preferably 3.0 g / (m 2 ·day), more preferably less than 2.0g / (m 2 In this way, a laminate having high gas barrier properties can be obtained even after retort treatment.

[0226] The composite elastic modulus and indentation hardness of the coating layer can be adjusted, for example, by the composition of the coating layer or the drying temperature during the formation of the coating layer. EXAMPLES

[0227] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these descriptions. First, the barrier films according to Examples 1 to 15 and Comparative Examples 1 to 6 were produced using the film-forming apparatus 10, which is the film-forming apparatus described in the present embodiment, and the film-forming method and coating layer forming process. Tables 1 and 2 summarize the pretreatment conditions, deposition conditions, etc.

[0228] Example 1 The polypropylene substrate for substrate 1 was a 20 μm-thick biaxially oriented polypropylene film (the first layer, which is the surface facing the deposition surface, is a 1.0 μm-thick layer made of a copolymer of propylene, ethylene, and butene, the second layer, which is the surface opposite the deposition surface, is a 1.0 μm-thick layer made of a copolymer of propylene, ethylene, and butene, the surface of the first layer was corona-treated, and the third layer (middle layer) was a homopolypropylene with a thickness of 18 μm).

[0229] Next, a coating liquid for forming an anchor coat layer, which was a mixture of a hydroxyl-containing (meth)acrylic resin and tolylene diisocyanate, was applied by a direct gravure method onto the first layer of the substrate 1 as a base layer, and then dried to form an anchor coat layer having a thickness of 0.2 μm.

[0230] After the anchor coat layer was formed, the film was rewound in a humidification process at 25° C. and 50% RH, and then stored at 25° C. and 50% RH for 3 days to condition the humidity.

[0231] In the film formation process, a vapor deposition film containing aluminum oxide was formed by a vacuum deposition method using a resistance heating type (RH in Table 1) evaporation mechanism 24 as shown in Fig. 6. Specifically, while aluminum metal wires were supplied into a boat 24b as a vapor deposition material, the vapor deposition material in the boat 24b was heated using the resistance heating type evaporation mechanism 24, and the aluminum was evaporated so as to reach the surface of the base material 1, and a vapor deposition film was formed on the surface of the base material 1 while supplying oxygen.

[0232] 6 and anodes (not shown) arranged on both sides of the width direction of the substrate 1 as viewed from the boat 24b and facing the opening of the hollow part of the hollow cathode 51 were used as the plasma supply mechanism 50. A plasma raw material gas (argon gas) was supplied to the hollow part of the hollow cathode 51, and a plasma was excited by discharging the plasma. The plasma was extracted by the opposing anode between the surface of the substrate 1 and the evaporation mechanism 24, and plasma assist was performed during deposition. The conditions for plasma assist were an amount of argon gas supplied to the hollow cathode of 80 sccm, an anode current of 48 A, and an anode voltage of 19 V. The cold trap was not operated, and a plasma post-treatment process was not performed after the plasma assist process during deposition.

[0233] By the above method, a vapor-deposited film was laminated on the substrate 1. The conveying speed was 600 m / min, and the thickness of the vapor-deposited film was 8.9 nm. The light transmittance at a wavelength of 366 nm measured in-line after vapor deposition was set to 100% based on the transmittance of the substrate 1 before vapor deposition, which was pretreated. Vapor deposition was then started, and the oxygen supply rate was feedback-controlled so that the light transmittance was 99.7%. The pressure during vapor deposition was 1.1 Pa.

[0234] The barrier film roll that had been subjected to the above-mentioned film-forming process was subjected to an aging treatment at 55°C and 50 RH% for 3 days.

[0235] Furthermore, a coating layer was laminated on the deposition film in the coating layer formation process. As a water-soluble polymer, polyvinyl alcohol with a saponification degree of 99% or more and a degree of polymerization of 2400 was mixed with a liquid of water and isopropyl alcohol in a ratio of 95 / 5 to obtain solution A adjusted to a solid content of 4%. Water, isopropyl alcohol, and 1N hydrochloric acid were mixed in a ratio of 65 / 34 / 1 to obtain an adjusted solution B. As a metal alkoxide, tetraethoxysilane was prepared as solution C. A liquid obtained by adjusting the ratio of solution B and solution C and mixing the liquid obtained by adjusting the ratio of solution A and solution D was used as a barrier coating agent. The ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the solid content of the barrier coating agent after mixing was 7%, and the mass of tetraethoxysilane converted to SiO2 was 2.5 relative to the solid content of PVA. This barrier coating agent was used as solution X.

[0236] The barrier coating agent prepared above was applied onto the vapor deposition film by a direct gravure method. It was then dried at 100°C to form a coating layer with a dry thickness of 300 nm. It was then aged at 55°C and 50% RH for 7 days to form a coating layer, thereby producing the barrier film of Example 1.

[0237] Example 2 The barrier film of Example 2 was produced in the same manner as in Example 1, except that plasma assistance was not performed in the film formation process.

[0238] Example 3 A barrier film of Example 3 was produced in the same manner as in Example 2, except that in the film-forming step, the conveying speed was 670 m / min, the thickness of the deposited film was 8.0 nm, the light transmittance was 94.0%, and the pressure was 0.3 Pa.

[0239] Example 4 A barrier film of Example 4 was produced in the same manner as in Example 3, except that the light transmittance was 88.0% and the pressure was 0.2 Pa in the film formation process.

[0240] Example 5 The barrier film of Example 5 was produced in the same manner as in Example 1, except that in the humidity adjustment process, the raw roll was rewound in an atmosphere of 30°C and 60% RH and then stored at 30°C and 60% RH for 3 days, and the aging treatment after the film formation process was performed at 60°C and 50% RH for 4 days.

[0241] Example 6 The barrier film of Example 6 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 2.25.

[0242] Example 7 The barrier film of Example 7 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 2.75.

[0243] Example 8 The barrier film of Example 8 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 3.0.

[0244] Example 9 The barrier film of Example 9 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 3.5.

[0245] Example 10 The barrier film of Example 10 was produced in the same manner as in Example 3, except that solution Y was used in the coating layer formation process. When mixing solutions B and C, 5% of glycidoxypropyltrimethoxysilane was added relative to the weight of tetraethoxysilane, and then solution Y was prepared as a barrier coating agent by mixing solutions B and C and solutions A and D while adjusting the ratios so that the solid content was 7% and the SiO2 equivalent mass of tetraethoxysilane was 2.5 relative to the solid content of PVA.

[0246] Example 11 The barrier film of Example 11 was produced in the same manner as in Example 10, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 3.5.

[0247] Example 12 The barrier film of Example 12 was produced in the same manner as in Example 3, except that solution Z was used in the coating layer formation process. When mixing solutions B and C, 8% of 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was added relative to the weight of tetraethoxysilane, and the ratio of solutions B and C and the ratio of solutions A and D were adjusted so that the coating layer had a solid content of 7% and the SiO2 equivalent mass of tetraethoxysilane relative to the solid content of PVA was 3.5, to produce a barrier coating agent called solution Z.

[0248] Example 13 A barrier film of Example 13 was produced in the same manner as in Example 3, except that the aging treatment after the coating layer formation step was not performed.

[0249] Example 14 The barrier film of Example 14 was produced in the same manner as in Example 13, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 3.5.

[0250] Example 15 The substrate 1 used was a substrate (total thickness 20 μm) that was stretched after multilayer co-extrusion of a polyamide resin as the underlayer, modified polypropylene as the first layer, homopolypropylene as the third layer, and a layer made of a copolymer of propylene and ethylene as the second layer, with the underlayer / first layer / third layer / second layer being 0.6 μm thick, the first layer was 1.5 μm thick, and the second layer was about 0.6 μm thick. Nylon 6 was used as the polyamide resin.

[0251] Thereafter, as a humidity conditioning step, the roll material was rewound in an atmosphere of 25° C. and 50% RH, and then stored at 25° C. and 50% RH for 3 days to condition the humidity.

[0252] The gas barrier film of Example 15 was produced by carrying out the film formation step and the coating layer formation step in the same manner as in Example 3, except that the following pretreatment step was carried out in the film formation step of Example 3. <Pretreatment process> The surface of the substrate 1 was subjected to plasma pretreatment using the plasma pretreatment mechanism 11B shown in Figures 2 and 3. Specifically, first, a plasma forming gas was supplied to the plasma pretreatment chamber 12B using a plasma raw material gas supply unit, while the air pressure in the plasma pretreatment chamber 12B was adjusted using the reduced pressure chamber 12. Next, a voltage was applied between the pretreatment roller 20 and the electrode unit 21 to generate plasma, and the surface of the substrate 1 was subjected to plasma pretreatment. The plasma pretreatment was performed under the following conditions. <Pretreatment conditions> Substrate conveying speed: 600m / min High frequency power output: 4kW High frequency power supply frequency: 40kHz Plasma intensity: 550W·sec / m 2 Plasma forming gas: Oxygen 100 (sccm), Argon 1000 (sccm) Magnetic forming means: 1000 gauss permanent magnet Voltage applied between pretreatment drum and plasma supply nozzle: 420V Pressure in pretreatment section: 2.0×10 -1 Pa

[0253] Example 16 As the substrate 1, a mixture of 50% by mass of a copolymer of metaxylenediamine and adipic acid as an underlayer, and a mixture of 50% by mass of a copolymer of dicarboxylic acid and hexamethylenediamine with a molar ratio of isophthalic acid / terephthalic acid of 2 / 1 (referred to as PA mixture in Table 1), an acid-modified polypropylene random copolymer as a first layer, homopolypropylene as a third layer, and a layer of a copolymer of propylene, ethylene, and butene as a second layer were co-extruded as underlayer / first layer / third layer / second layer, and then stretched 5 times in the longitudinal direction (MD direction) and 10 times in the transverse direction (TD direction) by a sequential biaxial stretching device to produce a 20 μm thick substrate film having an underlayer (0.7 μm), a first layer (1.5 μm), a third layer (17.1 μm), and a second layer (0.7 μm).

[0254] Thereafter, as a humidity conditioning step, the roll material was rewound in an atmosphere of 25° C. and 50% RH, and then stored at 25° C. and 50% RH for 3 days to condition the humidity.

[0255] The film formation process was carried out in the same manner as in Example 3, except that the aging treatment after the film formation process was carried out at 55° C. and 50% RH for 7 days.

[0256] The gas barrier film of Example 16 was produced without carrying out the subsequent coating layer forming step.

[0257] (Example 17) After the film-forming process of the gas barrier film of Example 16, a coating liquid for forming a coating layer (referred to as PU in Table 2) consisting of a mixture of a polyurethane emulsion and an emulsion of an oxazoline group-containing polymer was applied by a direct gravure method as a coating layer, and then dried to form a coating layer having a thickness of 200 nm. Then, an aging treatment was performed at 55°C and 50% RH for 7 days to produce the barrier film of Example 17.

[0258] Comparative Example 1 A barrier film of Comparative Example 1 was produced in the same manner as in Example 1, except that in the film formation process, a cold trap was operated and the plasma assist conditions were an anode current of 154 A and an anode voltage of 18 V.

[0259] Comparative Example 2 In the film formation process, the conditions of the plasma assist were the same as those of Comparative Example 1, except that the anode current was 140 A and the anode voltage was 16 V, and the barrier film of Comparative Example 2 was produced.

[0260] Comparative Example 3 The barrier film of Comparative Example 3 was produced in the same manner as in Example 5, except that an aging treatment after the film formation process was carried out at 60°C and 80 RH% for 5 days, and a sheet of approximately 210 mm x 300 mm cut from the roll was coated with the barrier coating agent using an applicator.

[0261] Comparative Example 4 The barrier film of Comparative Example 4 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the mass of tetraethoxysilane converted to SiO2 relative to the solid content of PVA was 1.5.

[0262] Comparative Example 5 The barrier film of Comparative Example 5 was produced in the same manner as in Example 3, except that in the coating layer formation step, the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the SiO2-equivalent mass of tetraethoxysilane relative to the solid content of PVA was 4.0.

[0263] Comparative Example 6 The barrier film of Comparative Example 6 was produced in the same manner as in Example 3, except that solution Z was used in the coating layer formation step, and the ratio of solution B to solution C and the ratio of solution A to solution D were adjusted so that the mass of tetraethoxysilane in terms of SiO2 relative to the solid content of PVA was 4.0.

[0264] [Table 1]

[0265]

Table 2

[0266] [Acquisition and Analysis of XAFS Spectrum] For the barrier films of Examples 1 to 15 and Comparative Examples 1 to 6, XAFS spectra were obtained from the surface side of the barrier film (from the surface side of the vapor deposition film or the coating layer) under the following measurement conditions. Among these, the results of Example 2 are shown in Fig. 9. The vertical axis in the figure is the intensity of the generated fluorescent X-ray (described as absorption intensity (a.u) in the figure), and the horizontal axis is the light (or X-ray) energy (eV).

[0267] [XAFS Spectrum Acquisition]< · Utilization line: BL1N2, Aichi Synchrotron Light Center · Acceleration energy: 1.2 GeV · Beam size: 1.0 mm (horizontal) × 1.0 mm (vertical) · Incident angle to the sample: 22.5° (assuming the vertical direction with respect to the sample is 0°) · Entrance slit: 30 μm · Exit slit: 30 μm · Measurement method: Partial fluorescence yield method · Energy range (Al K-edge): 1500 - 1700 eV · Energy step: 1500 - 1550 eV: 2.0 eV / step 1550 - 1555 eV: 1.0 eV / step 1555 - 1575 eV: 0.2 eV / step 1575 - 1600 eV: 0.5 eV / step 1600 - 1680 eV: 1.0 eV / step 1680 - 1700 eV: 2.0 eV / step (Integration time: all 10 s / point) · Energy calibration: Energy calibration using Au 4f 7 / 2 of the Au plate (calibration with the value obtained by subtracting the theoretical value of 1500 eV from the measured value)

[0268] <XAFS Spectrum Analysis> Peak Separation Method The intensity values were normalized so that the absorption spectrum intensity value at the energy value of 1557 eV of the absorbed X-ray was 0 and the absorption spectrum intensity value at the energy value of 1590 eV of the absorbed X-ray was 1.

[0269]

Number

[0270] Data points from 1555 eV to 1575 eV and from 1598 eV to 1602 eV of the normalized data points were extracted, and the above function f(x) was fitted to obtain each coefficient. However, the constraint conditions of k1 = k2, K1 = X1, and K2 = X2 were imposed. The fitting was performed by the least squares method. At this time, the least squares function of the scipy library in Python was used, and the initial values of the coefficients were obtained by giving values as shown in the following table. The definitions of the symbols of the above function are as follows. M i : Weight factor of the Gaussian function and the Lorentz function at the i-th absorption peak X i : Peak center at the i-th absorption peak h i : Peak intensity factor at the i-th absorption peak β i : Peak width factor at the i-th absorption peak k j : Baseline intensity factor at the j-th baseline K j : Half position of the baseline intensity at the j-th baseline

[0271]

Table 3

[0272] The results of peak separation of the XAFS spectra of Example 2 are shown in Fig. 10. Similarly, Fig. 11 shows the analysis results of separating the XAFS peaks of Example 3, Fig. 12 shows the analysis results of separating the XAFS peaks of Comparative Example 1, and Fig. 13 shows the analysis results of separating the XAFS peaks of Comparative Example 2.

[0273] Experiment is the measured XAFS spectrum, Fit.Peak1 is the intensity peak near 1566 eV separated, Fit.Peak2 is the intensity peak near 1568 eV separated, and Fit.Peak3 is the intensity peak near 1572 eV separated. From this, the calculation result of the XAFS peak top ratio P = (intensity peak top near 1572 eV) / (intensity peak top near 1566 eV) is shown in Table 4 for the barrier films of Examples 1 to 15 and Comparative Examples 1 to 6.

[0274] [Elemental analysis of the coating layer] For the coating layer surfaces of the barrier films of Examples 1 to 15 and Comparative Examples 1 to 6, narrow spectra of each element were measured using an X-ray photoelectron spectrometer (XPS). Then, etching of the surface after measurement was performed under the conditions described later to expose a new measurement surface. For the exposed measurement surface, narrow spectra of each element were measured under the same conditions. For the narrow spectra of C1s and Si2p, the background was subtracted by the Shirley method using analysis software to obtain the integrated intensity (area) of the peaks of each element. Using the obtained integrated intensity (area), the ratio of each element (element %) was calculated. The Si / C ratio was calculated from the ratio of each element after etching for 60 seconds × 2 times and is shown in Table 4. [X-ray photoelectron spectroscopy measurement conditions] Apparatus: ESCA3400 manufactured by Shimadzu Corporation X-ray source: MgKα Emission current: 20 mA Acceleration voltage: 10 kV Resolution: Low Measurement area: approximately 6 mmφ [Etching conditions] Ion species: Ar + Ar gas introduction pressure: 2.0×10 -2 Pa Emission current: 30mA Acceleration voltage: 0.3 kV Etching time: 60 seconds x 2 times

[0275] [Table 4]

[0276] <Evaluation of color unevenness on the outer edge of barrier film> A visual appearance inspection was carried out from the end face of the roll for each of the barrier films of Examples 1 to 15 and Comparative Examples 1 to 6. The results are shown in Table 5. Here, "visual appearance at the end" is an evaluation of color unevenness by visual inspection when viewed from the end (side) of the roll. When viewing the end of the barrier film roll, the dark-colored area (A) and the light-colored area (B) of the barrier film were sampled, and a Konica Minolta spectrophotometer CM-600d was used to place one sheet of the barrier film from the dark-colored area (A) on a standard white board with the film side facing up, and measurements were taken under conditions of SCI (including regular reflection light), 10° field of view, and D65 light source. The light-colored area (B) was also measured in the same manner, and the measured L * , a * , b * When the color difference between the dark colored area (A) and the light colored area (B) was calculated from the value of A, it was confirmed that when the color difference for one barrier film was 0.3 or more, a visual appearance inspection determined that there was severe color unevenness when viewed from the end face of the roll.

[0277] <Creating a laminate> For the barrier films of Examples 1 to 15 and Comparative Examples 1 to 6, the surface on the coating layer 130 side was bonded to a second biaxially oriented polypropylene film 140 (thickness: 20 μm) by dry lamination using a polyurethane-based two-component curing solvent-based adhesive, via a second adhesive layer 162. Furthermore, the surface of the barrier film opposite the coating layer 130 was bonded to a sealant layer (unstretched polypropylene film, 60 μm) by dry lamination using a two-component curing solvent-based adhesive, via a first adhesive layer 161, to produce the laminate of Example 1.

[0278] <Retort processing> The laminates of Examples 1 to 15 and Comparative Examples 1 to 6 were subjected to a retort treatment at 121° C. for 30 minutes and a high retort treatment at 135° C. for 30 minutes.

[0279] <Measurement of Barrier Properties of Barrier Films and Laminates> The water vapor permeability and oxygen permeability were measured for the barrier films and laminates using them of Examples 1 to 15 and Comparative Examples 1 to 6. The results are shown in Tables 5 and 6.

[0280] Oxygen permeability (cc / (m 2 The oxygen transmission rate (OTR) was measured in accordance with JIS K 7126-2 at 23°C and 90% RH using an oxygen transmission rate measuring device (manufactured by Mocon, product name OX-TRAN 2 / 20).

[0281] Water vapor permeability (g / (m 2 The water vapor transmission rate (WVTR) was measured in accordance with JIS K 7129 B method at 40°C and 100% RH using a water vapor transmission rate measuring device (manufactured by Mocon, product name "PERMATORAN-W 3 / 31").

[0282] <Measurement of composite elastic modulus and indentation hardness of coating layer> For the laminates of Examples 1 to 15 and Comparative Examples 1 to 6, the composite elastic modulus (GPa) and indentation hardness (GPa) of the coating layer of the laminates after heat sterilization treatment were measured under the following conditions. The results are shown in Tables 5 and 6. Measurement equipment: HYSITRON TI-950 Tribo Indenter Measurement location: From the cross-section side of the coating layer Measurement mode: Indentation Indenter: cubecorner indenter, TI-0037 Number of data points: 200 points / second Measurement Profile 0→10sec:0→15μN 10→15sec: 15μN 15→25sec:15→0μN

[0283] [Table 5]

[0284] [Table 6]

[0285] From Tables 5 and 6, it can be seen that the laminate using the barrier film using the polypropylene base material according to this embodiment, in which the peak top ratio P obtained from the XAFS spectrum is 1.05 or more and less than 1.60, has high barrier properties and reduced color unevenness after retort treatment.

[0286] It can also be seen that a laminate using a polypropylene base material having a composite elastic modulus of 5.0 GPa or more and 8.5 GPa or less and an indentation hardness of 0.9 GPa or more and 1.7 GPa or less has excellent oxygen barrier properties after retort treatment. [Explanation of symbols]

[0287] 110 (First) Polypropylene Base Material 115 Base layer 120 Evaporation film 130 Covering layer 140 Second polypropylene base material 150 Sealant Layer 161 First adhesive layer 162 Second adhesive layer 100, 200 laminate 100A Barrier Film 10 Film deposition equipment P Plasma X Rotation Axis 11A Substrate transport mechanism 11B Plasma pretreatment mechanism 11C Film formation mechanism 12 Decompression Chamber 12A Substrate transport chamber 12B Plasma pretreatment chamber 12C Deposition chamber 13 Unwinding roller 14a~d Guide roll 15 Winding roller 20 Pre-treatment roller 21 Electrode section 23 Magnetic field forming part 23a 1st page 23b 2nd side 231 First Magnet 231c 1st axis direction part 232 Second Magnet 232c 2nd axis direction part 232d Connection part 24 Evaporation mechanism 24b Boat 25 Coating roller 31 Power supply wiring 32 Power supply 35a~35c Bulkhead 50 Plasma supply mechanism 51 Hollow Cathode 61 Vapor deposition material supply section 63 Aluminum Vapor

Claims

1. A barrier film comprising a polypropylene substrate, a base layer, and an aluminum oxide vapor deposition film laminated in this order, a peak top ratio P of the aluminum oxide vapor-deposited film, as defined below, of 1.05 or more and less than 1.60 when X-ray absorption fine structure analysis is performed on the surface side of the barrier film opposite to the polypropylene substrate side. P = (peak intensity top near 1572 eV) / (peak intensity top near 1566 eV)

2. 2. The barrier film according to claim 1, further comprising a coating layer having a barrier property laminated on the aluminum oxide vapor-deposited film.

3. 3. The barrier film according to claim 2, wherein the coating layer has a ratio of silicon atoms to carbon atoms (Si / C) of 1.30 or more and 1.65 or less as measured by X-ray photoelectron spectroscopy (XPS).

4. The barrier film according to claim 1 , wherein the undercoat layer is an anchor coat layer formed on the polypropylene substrate.

5. 2. The barrier film according to claim 1, wherein the undercoat layer is a surface resin layer containing a polyamide resin formed on the polypropylene substrate.

6. the polypropylene base material has at least a first layer and a second layer as two surface layers, the first layer being formed on the undercoat layer side; the first layer comprises a copolymer of propylene and another monomer; The undercoat layer is the anchor coat layer, 5. The barrier film according to claim 4, wherein the first layer of the polypropylene base material, the anchor coat layer, the aluminum oxide vapor-deposited film, and the coating layer having barrier properties are laminated in this order.

7. the polypropylene base material has at least a first layer and a second layer as two surface layers, the first layer being formed on the undercoat layer side; the first layer comprises modified polypropylene; the undercoat layer is the surface resin layer containing the polyamide resin, 6. The barrier film according to claim 5, wherein the first layer of the polypropylene base material, the surface resin layer containing the polyamide resin, the aluminum oxide vapor-deposited film, and the coating layer having barrier properties are laminated in this order.

8. the polypropylene base material has at least a first layer and a second layer as two surface layers, the second layer being formed on a surface opposite to the undercoat layer side, the second layer comprises a copolymer of propylene and another monomer; 2. The barrier film according to claim 1, wherein the first layer of the polypropylene base material, the undercoat layer, the aluminum oxide vapor-deposited film, and the coating layer having barrier properties are laminated in this order.

9. A heat-sterilized laminate comprising the barrier film according to any one of claims 1 to 8 and a sealant layer, the laminate being used for a packaging bag for containing retort food or boiled food, A laminate, wherein the coating layer of the laminate has a composite elastic modulus and an indentation hardness, as measured by a nanoindentation method from a cross-section of the coating layer, of which the composite elastic modulus is 5.0 GPa or more and 8.5 GPa or less, and the indentation hardness is 0.9 GPa or more and 1.7 GPa or less.

10. A packaging product comprising the laminate of claim 9.

Citation Information

Patent Citations

  • Laminate film and method for manufacturing the same

    JP2017177343A

  • Method for manufacturing gas barrier film and gas barrier film

    JP2022052319A

  • Gas barrier multilayer body and packaging material

    WO2022085586A1